Resin composition, cured product of resin composition, resin sheet, printed wiring board, semiconductor chip package, and semiconductor device

By controlling the ratio of the average thermal expansion coefficient and crosslinking density in the resin composition, and using epoxy resin and hardener, the deformation problem caused by uneven stress during the packaging process is solved, and long-term reliability is improved, and effective packaging and protection of semiconductor chips is achieved.

JP7647825B2Active Publication Date: 2025-03-18AJINOMOTO CO INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023148495
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-18
Estimated Expiration
2040-03-31

AI Technical Summary

Technical Problem

When packaging a semiconductor chip, there is a problem of deformation caused by uneven stress, and the use of a resin composition containing a thermoplastic resin can reduce the elastic modulus of the cured product to suppress deformation, but its long-term reliability is poor.

Method used

By controlling the ratio of the average linear thermal expansion coefficient and crosslinking density in the resin composition, it is ensured that its value after 90 minutes of heating at 180°C is within the range of 145

Benefits of technology

It effectively suppresses deformation during the packaging process, improves the long-term reliability of the resin composition, and is suitable for packaging and protection of various electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647825000001
    Figure 0007647825000001
  • Figure 0007647825000002
    Figure 0007647825000002
  • Figure 0007647825000003
    Figure 0007647825000003
Patent Text Reader

Abstract

To provide a resin composition capable of obtaining a cured product having suppressed warpage and excellent in long-term reliability; and to provide the cured product thereof, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device.SOLUTION: A resin composition comprises (A) an epoxy resin and (B) a curing agent, wherein a value Zf (ppm_cm3 / mol_K) obtained by dividing an average linear thermal expansion coefficient α of the cured product by a cross-linking density n of the cured product satisfies 145<Zf<1,300.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device. [Background technology]

[0002] A printed wiring board for a semiconductor device usually includes an insulating layer. A resin composition is used as an insulating material constituting this insulating layer. Patent Document 1 discloses an insulating material containing a thermosetting compound and a curing agent (see claim 1). Such a resin composition may also be used to seal a semiconductor chip. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-188667 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] When encapsulating a semiconductor chip (particularly when encapsulating one side of the semiconductor chip), warping can occur due to uneven stress. Therefore, it is necessary to suppress warping.

[0005] By the way, a thermoplastic resin may be included in the resin composition. And, by including a thermoplastic resin in the resin composition, the elastic modulus of the cured product of the resin composition is reduced, and as a result, it is expected that warpage occurring in the semiconductor chip is suppressed. However, as a result of the study by the present inventor, it was found that the use of a resin composition containing a thermoplastic resin may result in poor long-term reliability. Here, the long-term reliability can be confirmed, for example, by subjecting a test piece to an HTS test (High Thermal Storage test), comparing the physical properties before and after the test, and finding that the degree of change is small. That is, it was found that in order to suppress warpage and to provide excellent long-term reliability, it is insufficient to only adjust the elastic modulus of the cured product of the resin composition. Therefore, if adjustment items other than the elastic modulus can be obtained, it is expected that it will be possible to provide a resin composition that can suppress warpage and obtain a cured product with excellent long-term reliability, regardless of the presence or absence of a thermoplastic resin or the content of the thermoplastic resin.

[0006] An object of the present invention is to provide a resin composition which is capable of giving a cured product which is suppressed in warping and has excellent long-term reliability; and a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device. [Means for solving the problem]

[0007] The present inventors have conducted extensive research into a resin composition containing (A) an epoxy resin and (B) a curing agent, and have found that the average linear thermal expansion coefficient α of the cured product of the resin composition and the crosslink density n of the cured product are used as parameters, and the value Z obtained by dividing the average linear thermal expansion coefficient α by the crosslink density n is f (ppm cm 3 / mol K) is 145 <Z f It has been found that the above-mentioned problems can be solved by satisfying the condition <1300, and this has led to the completion of the present invention.

[0008] That is, the present invention includes the following. [1] A resin composition comprising (A) an epoxy resin and (B) a curing agent, The resin composition was cured at 180°C for 90 minutes to obtain a cured product, and the average linear thermal expansion coefficient α (ppm / K) was calculated based on the crosslink density n (mol / cm 3 ) divided by Z f (ppm cm 3 / mol K) is expressed by the following formula: 145 <Z f <1300 The resin composition satisfies the above requirements. [2] The resin composition according to [1], further comprising (C) an inorganic filler. [3] The resin composition according to [2], wherein the content of the (C) component is 70 mass% or more, based on 100 mass% of the non-volatile components in the resin composition. [4] The resin composition according to [2] or [3], wherein the average particle size of component (C) is 10 μm or less. [5] The resin composition according to any one of [1] to [4], wherein component (B) contains a maleimide compound having at least one hydrocarbon chain selected from the group consisting of an alkyl group having 5 or more carbon atoms which may have a substituent and an alkylene group having 5 or more carbon atoms which may have a substituent in the molecule. [6] The resin composition according to any one of [1] to [5], wherein the content of component (B) is 0.5% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition. [7] The resin composition according to any one of [1] to [6], further comprising (D) a thermoplastic resin. [8] The resin composition according to [7], wherein the content of the (D) component is 25 mass% or less, based on 100 mass% of the non-volatile components in the resin composition. [9] The resin composition according to any one of [1] to [8], wherein the glass transition temperature Tg of the cured product is within a range of 150 to 240°C.

[10] The resin composition according to any one of [1] to [9], wherein the cured product has an average linear thermal expansion coefficient α of 25 ppm / K or less.

[11] The storage modulus E' of the cured product at a given temperature T (K) is 1.50 × 10 9The resin composition according to any one of [1] to

[10] , wherein the predetermined temperature T (K) is a temperature that is the sum of the glass transition temperature Tg (°C) of the cured product and 353 (K).

[12] The crosslink density n of the cured product is 0.15 mol / cm 3 The resin composition according to any one of [1] to

[11] below.

[13] The value Z f But the following formula: 150≦Z f <≦1000 The resin composition according to any one of [1] to

[12] , which satisfies the above.

[14] The resin composition according to any one of [1] to

[13] , which is for forming an insulating layer.

[15] The resin composition according to any one of [1] to

[14] , which is for forming a solder resist layer.

[16] A cured product of the resin composition according to any one of [1] to

[15] .

[17] A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to

[15] .

[18] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to

[15] or the cured product according to

[16] .

[19] A semiconductor chip package comprising the printed wiring board according to

[18] and a semiconductor chip mounted on the printed wiring board.

[20] A semiconductor chip package comprising: a semiconductor chip; and a cured product of the resin composition according to any one of [1] to

[15] or the cured product according to

[16] that encapsulates the semiconductor chip.

[21] A semiconductor device comprising the printed wiring board according to

[18] or the semiconductor chip package according to

[19] or

[20] . Effect of the Invention

[0009] According to the present invention, it is possible to provide a resin composition which is capable of giving a cured product which is suppressed in warping and has excellent long-term reliability; and a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The resin composition of the present invention, a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device will be described in detail below.

[0011] [Resin composition] The resin composition of the present invention is a resin composition containing (A) an epoxy resin and (B) a curing agent, and the resin composition is cured at 180°C for 90 minutes to obtain a cured product, and the average linear thermal expansion coefficient α is divided by the crosslink density n of the cured product to obtain a value Z f (ppm cm 3 / mol·K) is within the numerical range described below. This resin composition can provide a cured product that is suppressed in warping and has excellent long-term reliability. By using such a resin composition, it is possible to provide a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device.

[0012] The resin composition of the present invention may further contain an optional component in combination with the components (A) and (B). Examples of the optional components include an inorganic filler (C), a thermoplastic resin (D), a curing accelerator (E), and other additives (F) (excluding the components (A) to (E)). Each component contained in the resin composition will be described in detail below. In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are 100 mass %, unless otherwise specified.

[0013] <(A) Epoxy resin> The resin composition contains an epoxy resin (A). An epoxy resin is a resin having one or more epoxy groups in the molecule. When the resin composition contains the epoxy resin (A), a cured product having a crosslinked structure can be obtained.

[0014] Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more.

[0015] The epoxy resin preferably contains an epoxy resin having two or more epoxy groups in the molecule. When the non-volatile component of the epoxy resin is taken as 100 mass %, it is preferable that 50 mass % or more is an epoxy resin having two or more epoxy groups in the molecule.

[0016] The epoxy resin may be a liquid epoxy resin (A-1) or a solid epoxy resin (A-2). The resin composition may contain a combination of the liquid epoxy resin (A-1) and the solid epoxy resin (A-2).

[0017] ((A-1) Liquid epoxy resin) (A-1) liquid epoxy resin refers to an epoxy resin that is liquid at a temperature of 20° C. The resin composition preferably contains (A-1) liquid epoxy resin. Here, liquid epoxy resin is one of the components that tends to lower the glass transition temperature of the cured product of the resin composition, but according to the present invention, even if the resin composition contains such a component, it is possible to obtain a cured product that has a sufficiently low average linear thermal expansion coefficient and excellent heat resistance.

[0018] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in the molecule, and more preferably an aromatic liquid epoxy resin having two or more epoxy groups in the molecule. In the present invention, the aromatic epoxy resin means an epoxy resin having an aromatic ring in the molecule.

[0019] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, glycidyl amine type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin is more preferred.

[0020] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP-4032-SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "YX7400" (flexible epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "630" and "630LS" manufactured by Mitsubishi Chemical Corporation. Examples of epoxy resins include "ZX1059" (a mixture of bisphenol A and bisphenol F epoxy resins) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "EX-721" (a glycidyl ester epoxy resin) manufactured by Nagase ChemteX Corporation; "Celloxide 2021P" (an alicyclic epoxy resin having an ester structure) manufactured by Daicel Corporation; "PB-3600" (an epoxy resin having a butadiene structure) manufactured by Daicel Corporation; and "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane epoxy resins) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd. These may be used alone or in combination of two or more.

[0021] The content of the (A-1) component in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and particularly preferably 2% by mass or more, when the non-volatile components in the resin composition are 100% by mass, from the viewpoint of obtaining the effects of including the (A-1) component (for example, improved handling of the resin varnish, improved compatibility). The upper limit of the content of the (A-1) component is not particularly limited as long as the effects of the present invention are not excessively impaired, but may be 40% by mass or less, 35% by mass or less, 30% by mass or less, or 25% by mass or less.

[0022] ((A-2) Solid epoxy resin) The solid epoxy resin refers to an epoxy resin that is solid at a temperature of 20° C. The resin composition may contain only the solid epoxy resin (A-2) as the component (A), but from the viewpoint of lowering the average linear thermal expansion coefficient or increasing the crosslinking density, it is preferable to contain the solid epoxy resin (A-2) in combination with the liquid epoxy resin (A-1). As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in the molecule is preferable.

[0023] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and naphthol type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, and biphenyl type epoxy resin are more preferred.

[0024] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200L", "HP-7200", "HP-7200HH", and "HP-7200H" (dicyclopentadiene epoxy resins) manufactured by DIC Corporation. type epoxy resin); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin) manufactured by DIC; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku; "NC3000H", "NC3000", "NC3000L", NC3100 (biphenyl type epoxy resin); Nippon Steel & Sumitomo Metal Chemical's ESN475V (naphthol type epoxy resin); Nippon Steel & Sumitomo Metal Chemical's ESN485 (naphthol novolac type epoxy resin); Mitsubishi Chemical's YX4000H, YX4000, and YL6121 (biphenyl type epoxy resin); Mitsubishi Chemical's YX4000HK (bixylenol type epoxy resin); Mitsubishi Chemical's YX8800 (anthracene type epoxy resin); Osaka Examples of epoxy resins include "PG-100" and "CG-500" manufactured by Gas Chemicals Corporation; "157S70" (bisphenol A novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more.

[0025] The content of the (A-2) component in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.2% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining the effects of including the (A-2) component (for example, a decrease in the average linear thermal expansion coefficient, an improvement in heat resistance, or a good crosslink density). The upper limit of the content of the (A-2) component is not particularly limited as long as the effects of the present invention are not excessively impaired, but from the viewpoint of appropriately suppressing the crosslink density, it may be 10% by mass or less, 8% by mass or less, 5% by mass or less, or 3% by mass or less.

[0026] When the liquid epoxy resin (A-1) and the solid epoxy resin (A-2) are used in combination as the component (A), the ratio of the amounts thereof (liquid epoxy resin: solid epoxy resin) is preferably in the range of 1:0.01 to 1:20 by mass. By setting the ratio of the liquid epoxy resin (A-1) and the solid epoxy resin (A-2) in this range, the following effects can be obtained: i) when used in the form of a resin sheet, appropriate adhesion is provided; ii) when used in the form of a resin sheet, sufficient flexibility is obtained and handling is improved; and iii) a cured product having sufficient breaking strength can be obtained. From the viewpoint of obtaining the above effects i) to iii) and from the viewpoint of appropriately suppressing the crosslinking density, the ratio of the liquid epoxy resin (A-1) and the solid epoxy resin (A-2) (liquid epoxy resin: solid epoxy resin) is more preferably in the range of 1:0.01 to 1:10 by mass, and even more preferably in the range of 1:0.01 to 1:8.

[0027] From the viewpoint of achieving the intended effects of the present invention, the content of the (A) component in the resin composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and particularly preferably 3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit of the epoxy resin content is not particularly limited as long as the effects of the present invention are achieved, but may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 35% by mass or less.

[0028] The epoxy equivalent of the (A) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 70 g / eq. to 2000 g / eq., and even more preferably 70 g / eq. to 1000 g / eq. When it is in this range, the crosslink density of the cured product is sufficient, and a cured product having excellent strength and heat resistance can be obtained. The epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing one equivalent of epoxy groups.

[0029] The weight average molecular weight of the component (A) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0030] <(B) Hardener> The resin composition contains a curing agent (B). As the component (B), a substance having a function of curing the component (A) can be used. When the resin composition contains the curing agent (B) together with the epoxy resin (A), a cured product having excellent heat resistance can be obtained.

[0031] Examples of the (B) curing agent include (B-1) maleimide-based curing agents and (B-2) curing agents other than maleimide-based curing agents. (B-2) Curing agents other than maleimide-based curing agents include one or more curing agents selected from active ester-based curing agents, phenol-based curing agents, naphthol-based curing agents, carbodiimide-based curing agents, benzoxazine-based curing agents, acid anhydride-based curing agents, amine-based curing agents, and cyanate ester-based curing agents (excluding curing agents containing a maleimide group). The curing agents may be used alone or in combination of two or more.

[0032] Among them, from the viewpoint of achieving the intended effect of the present invention, it is preferable that the (B) component contains a maleimide-based curing agent (B-1). It is also preferable that the (B) component contains a maleimide-based curing agent (B-1) and one or more curing agents selected from a curing agent other than a maleimide-based curing agent (B-2). More preferably, the (B) component contains a maleimide-based curing agent (B-1) and one or more curing agents selected from an active ester-based curing agent and a phenol-based curing agent as the (B-2) component.

[0033] ((B-1) Maleimide-based curing agent) The maleimide-based curing agent may be a maleimide compound having at least one of a hydrocarbon chain of an alkyl group having 5 or more carbon atoms, which may have a substituent, and an alkylene group having 5 or more carbon atoms, which may have a substituent, in the (B-1a) molecule. The maleimide-based curing agent may be a maleimide-based curing agent other than the (B-1a) component (B-1b). The maleimide-based curing agent may be used alone or in combination of two or more. The maleimide-based curing agent preferably contains the (B-1a) component, and may further contain the (B-1b) component in combination.

[0034] The component (B-1) is a compound containing at least one maleimide group represented by the following formula in the molecule, and is preferably an aliphatic structure-containing maleimide compound. In the structure shown in the following formula, one of the three bonds of the nitrogen atom that is not bonded to other atoms represents a single bond.

[0035] [ka]

[0036] The number of maleimide groups per molecule in component (B-1) is 1 or more, and from the viewpoint of enhancing the intended effects of the present invention, is preferably 2 or more, and more preferably 3 or more, and while there is no upper limit, it can be 10 or less, 6 or less, 4 or less, or 3 or less.

[0037] The number of carbon atoms of the alkyl group having 5 or more carbon atoms in the aliphatic structure-containing maleimide compound is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. The alkyl group may be linear, branched, or cyclic, and linear is preferred. Examples of such alkyl groups include pentyl, hexyl, heptyl, octyl, nonyl, and decyl groups. The alkyl group having 5 or more carbon atoms may be a substituent of an alkylene group having 5 or more carbon atoms.

[0038] The number of carbon atoms of the alkylene group having 5 or more carbon atoms is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. The alkylene group may be linear, branched, or cyclic, and linear is preferred. Here, the cyclic alkylene group is a concept that includes the case where it is composed of only a cyclic alkylene group and the case where it contains both a linear alkylene group and a cyclic alkylene group. Examples of such alkylene groups include pentylene, hexylene, heptylene, octylene, nonylene, decylene, undecylene, dodecylene, tridecylene, heptadecylene, hexatriacontylene, a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0039] From the viewpoint of enhancing the intended effects of the present invention, the aliphatic structure-containing maleimide compound is a maleimide compound having at least one hydrocarbon chain selected from the group consisting of an alkyl group having 5 or more carbon atoms which may have a substituent and an alkylene group having 5 or more carbon atoms which may have a substituent in the (B-1a) molecule, and is preferably a maleimide compound having both an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms.

[0040] The alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms may be linear, but at least some of the carbon atoms may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a condensed ring. Examples of the ring formed by bonding to each other include a cyclohexane ring and the like.

[0041] The alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms may or may not have a substituent. Examples of the substituent include a halogen atom, -OH, -O-C 1-10 alkyl group, -N(C 1-10 alkyl group)2, C 1-10 alkyl group, C 6-10 aryl group, -NH2, -CN, -C(O)O-C 1-10 alkyl group, -COOH, -C(O)H, -NO2 and the like. Here, the term "C x-y " (x and y are positive integers and satisfy x < y) represents that the number of carbon atoms of the organic group described immediately after this term is x to y. For example, the expression "C 1-10 alkyl group" indicates an alkyl group having 1 to 10 carbon atoms. These substituents may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a condensed ring. Here, the number of carbon atoms of the substituent is not included in the number of carbon atoms of the alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms. The above-mentioned substituents may further have a substituent (hereinafter sometimes referred to as "secondary substituent"). Unless otherwise specified, the same substituents as those described above may be used as the secondary substituent.

[0042] In the aliphatic structure-containing maleimide compound, the alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms are preferably directly bonded to the nitrogen atom of the maleimide group.

[0043] The number of maleimide groups per molecule of the aliphatic structure-containing maleimide compound may be 1, but is preferably 2 or more, preferably 10 or less, more preferably 6 or less, and particularly preferably 3 or less. When the aliphatic structure-containing maleimide compound has 2 or more maleimide groups per molecule, the intended effects of the present invention can be enhanced.

[0044] The aliphatic structure-containing maleimide compound is preferably a maleimide compound represented by the following general formula (B1).

Chemical formula

[0045] M represents an alkylene group having 5 or more carbon atoms which may have a substituent. The alkylene group of M is the same as the above-described alkylene group having 5 or more carbon atoms. Examples of the substituent of M include a halogen atom, -OH, -O-C 1-10 alkyl group, -N(C 1-10 alkyl group)2, C 1-10 alkyl group, C 6-10 aryl group, -NH2, -CN, -C(O)O-C 1-10 alkyl group, -COOH, -C(O)H, -NO2, etc. Here, the term "C x-y " (x and y are positive integers and satisfy x < y) represents that the carbon atom number of the organic group described immediately after this term is x to y. For example, the expression "C 1-10 alkyl group" indicates an alkyl group having 1 to 10 carbon atoms. These substituents may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a condensed ring. The above-described substituents may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). As the secondary substituent, the same ones as the above-described substituents may be used unless otherwise specified. The substituent of M is preferably an alkyl group having 5 or more carbon atoms. Here, the carbon atom number of the substituent is not included in the carbon atom number of the alkylene group having 5 or more carbon atoms.

[0046] L represents a single bond or a divalent linking group. Examples of the divalent linking group include an alkylene group, an alkenylene group, an alkynylene group, an arylene group, -C(=O)-, -C(=O)-O-, -NR 0 -(R 0 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, an oxygen atom, a sulfur atom, or C(=O)NR 0 -, a divalent group derived from phthalimide, a divalent group derived from pyromellitic diimide, and a group consisting of a combination of two or more of these divalent groups. The alkylene group, the alkenylene group, the alkynylene group, the arylene group, the divalent group derived from phthalimide, the divalent group derived from pyromellitic diimide, and a group consisting of a combination of two or more of these divalent groups may have an alkyl group having 5 or more carbon atoms as a substituent.

[0047] The divalent group derived from phthalimide refers to a divalent group derived from phthalimide, specifically a group represented by the following general formula: In the formula, "*" represents a bond. [ka]

[0048] The divalent group derived from pyromellitic diimide refers to a divalent group derived from pyromellitic diimide, specifically, a group represented by the following general formula: In the formula, "*" represents a bond. [ka]

[0049] The alkylene group as the divalent linking group in L is preferably an alkylene group having 1 to 50 carbon atoms, more preferably an alkylene group having 1 to 45 carbon atoms, and particularly preferably an alkylene group having 1 to 40 carbon atoms. This alkylene group may be linear, branched, or cyclic. Examples of such alkylene groups include a methylethylene group, a cyclohexylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, a decylene group, an undecylene group, a dodecylene group, a tridecylene group, a heptadecylene group, a hexatriacontylene group, a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0050] The alkenylene group as the divalent linking group in L is preferably an alkenylene group having 2 to 20 carbon atoms, more preferably an alkenylene group having 2 to 15 carbon atoms, and particularly preferably an alkenylene group having 2 to 10 carbon atoms. This alkenylene group may be linear, branched, or cyclic. Examples of such alkenylene groups include a methylethylenylene group, a cyclohexenylene group, a pentenylene group, a hexenylene group, a heptenylene group, and an octenylene group.

[0051] The alkynylene group as the divalent linking group in L is preferably an alkynylene group having 2 to 20 carbon atoms, more preferably an alkynylene group having 2 to 15 carbon atoms, and particularly preferably an alkynylene group having 2 to 10 carbon atoms. This alkynylene group may be linear, branched, or cyclic. Examples of such alkynylene groups include a methylethynylene group, a cyclohexynylene group, a pentynylene group, a hexynylene group, a heptynylene group, and an octynylene group.

[0052] The arylene group as the divalent linking group in L is preferably an arylene group having 6 to 24 carbon atoms, more preferably an arylene group having 6 to 18 carbon atoms, still more preferably an arylene group having 6 to 14 carbon atoms, and even more preferably an arylene group having 6 to 10 carbon atoms. Examples of the arylene group include a phenylene group, a naphthylene group, and an anthracenylene group.

[0053] The alkylene group, alkenylene group, alkynylene group, and arylene group, which are the divalent linking groups in L, may have a substituent. The substituent is the same as the substituent of M in general formula (B1), and is preferably an alkyl group having 5 or more carbon atoms.

[0054] Examples of the group consisting of a combination of two or more divalent groups in L include a divalent group consisting of a combination of an alkylene group, a divalent group derived from phthalimide, and an oxygen atom; a divalent group consisting of a combination of a divalent group derived from phthalimide, an oxygen atom, an arylene group, and an alkylene group; a divalent group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; and the like. The group consisting of a combination of two or more divalent groups may form a ring such as a condensed ring by the combination of the respective groups. In addition, the group consisting of a combination of two or more divalent groups may be a repeating unit having a repeating unit number of 1 to 10.

[0055] Among them, L in the general formula (B1) is preferably an oxygen atom, an arylene group having 6 to 24 carbon atoms which may have a substituent, an alkylene group having 1 to 50 carbon atoms which may have a substituent, an alkyl group having 5 or more carbon atoms, a divalent group derived from phthalimide, a divalent group derived from pyromellitic diimide, or a divalent group consisting of a combination of two or more of these groups. Among them, L is more preferably an alkylene group; a divalent group having a structure of an alkylene group-a divalent group derived from phthalimide-oxygen atom-a divalent group derived from phthalimide; a divalent group having a structure of an alkylene group-a divalent group derived from phthalimide-oxygen atom-arylene group-alkylene group-arylene group-oxygen atom-a divalent group derived from phthalimide; or a divalent group having a structure of an alkylene-a divalent group derived from pyromellitic diimide.

[0056] The aliphatic structure-containing maleimide compound is preferably a maleimide compound represented by the following general formula (B2). [ka] In general formula (B2), M 1 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, each A independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and t represents an integer of 1 to 10.

[0057] M 1 Each of M independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. 1 is the same as M in general formula (B1).

[0058] Each A independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, or a divalent group having an aromatic ring which may have a substituent. The alkylene group in A may be any of linear, branched, and cyclic, and among them, a cyclic alkylene group having 5 or more carbon atoms which may have a substituent is preferred. The number of carbon atoms of the alkylene group is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. Examples of such alkylene groups include a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0059] Examples of the aromatic ring in the divalent group having an aromatic ring represented by A include a benzene ring, a naphthalene ring, an anthracene ring, a phthalimide ring, a pyromellitic diimide ring, and an aromatic heterocycle, and the like are mentioned, with a benzene ring, a phthalimide ring, and a pyromellitic diimide ring being preferred. That is, the divalent group having an aromatic ring is preferably a divalent group having a benzene ring which may have a substituent, a divalent group having a phthalimide ring which may have a substituent, or a divalent group having a pyromellitic diimide ring which may have a substituent. Examples of the divalent group having an aromatic ring include a group consisting of a combination of a divalent group derived from phthalimide and an oxygen atom; a group consisting of a combination of a divalent group derived from phthalimide, an oxygen atom, an arylene group, and an alkylene group; a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; a divalent group derived from pyromellitic diimide; a group consisting of a combination of a divalent group derived from phthalimide and an alkylene group; and the like. The arylene group and alkylene group are the same as the arylene group and alkylene group in the divalent linking group represented by L in general formula (B1).

[0060] The alkylene group and the divalent group having an aromatic ring represented by A may have a substituent. The substituent is the same as the substituent represented by the substituent of M in the general formula (B1).

[0061] Specific examples of the group represented by A include the following groups: In the formula, "*" represents a bond. [ka] [ka]

[0062] The maleimide compound represented by general formula (B2) is preferably either a maleimide compound represented by the following general formula (B2-1) or a maleimide compound represented by the following general formula (B2-2). [ka] In general formula (B2-1), M 2 and M 3 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, and each R30 independently represents an oxygen atom, an arylene group, an alkylene group, or a divalent group consisting of a combination of two or more of these groups. t1 represents an integer of 1 to 10. [ka] In general formula (B2-2), M 4 , M 6 and M 7 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent; M 5 each independently represents a divalent group having an aromatic ring which may have a substituent; R 31 and R 32 each independently represents an alkyl group having 5 or more carbon atoms. t2 represents an integer of 0 to 10, and u1 and u2 each independently represent an integer of 0 to 4.

[0063] M 2 and M 3 Each of M independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. 2 and M 3is the same as the alkylene group having 5 or more carbon atoms represented by M in general formula (B1), and a hexatriacontylene group is preferred.

[0064] R 30 R each independently represents an oxygen atom, an arylene group, an alkylene group, or a group consisting of a combination of two or more of these divalent groups. The arylene group and the alkylene group are the same as the arylene group and the alkylene group in the divalent linking group represented by L in the general formula (B1). 30 is preferably an oxygen atom or a group formed from a combination of two or more divalent groups.

[0065] R 30 In the formula, examples of the group consisting of a combination of two or more divalent groups include a combination of an oxygen atom, an arylene group, and an alkylene group. Specific examples of the group consisting of a combination of two or more divalent groups include the following groups. In the formula, "*" represents a bond. [ka]

[0066] M 4 , M 6 and M 7 Each of M independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. 4 , M 6 and M 7 is the same as the alkylene group having 5 or more carbon atoms which may have a substituent represented by M in general formula (B1), and is preferably a hexylene group, a heptylene group, an octylene group, a nonylene group or a decylene group, and more preferably an octylene group.

[0067] M 5 Each of M independently represents a divalent group having an aromatic ring which may have a substituent. 5is the same as the divalent group having an aromatic ring which may have a substituent represented by A in general formula (B2), and is preferably a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; a group consisting of a combination of a divalent group derived from phthalimide and an alkylene group, and more preferably a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide.

[0068] M 5 Specific examples of the group represented by the formula include the following groups: In the formula, "*" represents a bond. [ka]

[0069] R 31 and R 32 R each independently represents an alkyl group having 5 or more carbon atoms. 31 and R 32 is the same as the above-mentioned alkyl group having 5 or more carbon atoms, and is preferably a hexyl group, a heptyl group, an octyl group, a nonyl group, or a decyl group, and more preferably a hexyl group or an octyl group.

[0070] Each of u1 and u2 independently represents an integer of 1 to 15, and an integer of 1 to 10 is preferable.

[0071] Specific examples of the aliphatic structure-containing maleimide compound include the following compounds (b1), (b2), (b3), and (b4). However, the aliphatic structure-containing maleimide compound is not limited to these specific examples. In the formulas (b1), (b2), and (b3), n9, n10, and n11 each represent an integer of 1 to 10. [ka] [ka] [ka] [ka]

[0072] Specific examples of the aliphatic structure-containing maleimide compound (component (B-1)) include "BMI-1500" (compound of formula (b1)), "BMI-1700" (compound of formula (b2)), "BMI-3000J" (compound of formula (b3)), and "BMI-689" (compound of formula (b4)), all of which are manufactured by Designer Molecules, Inc.

[0073] From the viewpoint of significantly obtaining the intended effects of the present invention, the maleimide group equivalent of the component (B-1) is preferably 50 g / eq. to 2000 g / eq., more preferably 100 g / eq. to 1000 g / eq., and even more preferably 150 g / eq. to 500 g / eq. The maleimide group equivalent is the mass of a maleimide compound containing one equivalent of a maleimide group.

[0074] The content of the (B-1) component depends on the content of components other than the (A) component and the (B-1) component when the non-volatile components of the resin composition are taken as 100% by mass, but from the viewpoint of enhancing the intended effects of the present invention, it may be 0.2% by mass or more, 0.5% by mass or more, 1.0% by mass or more, or 2.0% by mass or more. From the viewpoint of enhancing the intended effects of the present invention, the upper limit is preferably 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less. From the viewpoint of enhancing the intended effects of the present invention, the ratio of the (B-1) component to the (B) component is preferably 30% by mass or more, 40% by mass or more, or 50% by mass or more, and the upper limit is 100% by mass.

[0075] ((B-2) Curing agents other than maleimide-based curing agents) The active ester curing agent is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0076] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing an acetylated product of phenol novolac, and active ester compounds containing a benzoylated product of phenol novolac are preferred, and among these, active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0077] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "HPC-8000L-65TM" (manufactured by DIC Corporation); active ester compounds containing a naphthalene structure, such as "EXB-9416-70BK", "EXB-8100L-65T", "EXB-8150-65T", "EXB-8150L-65T", "HPC-8150-60T", "HPC-8150-62T", and "HP-B-8151-62T" (manufactured by DIC Corporation); and phenol novolac. Examples of the active ester compound containing an acetylated product of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester compound containing a benzoylated product of phenol novolac includes "YLH1026" (manufactured by Mitsubishi Chemical Corporation), an active ester curing agent which is an acetylated product of phenol novolac includes "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester curing agent which is a benzoylated product of phenol novolac includes "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group includes "PC1300-02-65MA" (manufactured by Air Water Corporation).

[0078] As the phenol-based curing agent (excluding active ester compounds) and naphthol-based curing agent (excluding active ester compounds), from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a cresol novolac structure, or a naphthol-based curing agent having a novolac structure is preferred. Also, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenol-based curing agent is preferred, and a triazine skeleton-containing phenol-based curing agent is more preferred.

[0079] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500", and "KA-1160" manufactured by DIC Corporation.

[0080] Specific examples of carbodiimide-based curing agents include "V-03", "V-05", "V-07", "V-09", and "Elastostab H01" manufactured by Nisshinbo Chemical Inc.

[0081] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation, "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd. The benzoxazine-based curing agent is a compound having a benzoxazine structure. The benzoxazine structure refers to a substituted or unsubstituted benzoxazine ring (e.g., 1,2-benzoxazine ring, 1,3-benzoxazine ring), or a benzoxazine ring in which a part of the double bond is hydrogenated (e.g., 3,4-dihydro-2H-1,3-benzoxazine ring). Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include polymeric acid anhydrides such as biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and styrene-maleic acid resins, which are copolymers of styrene and maleic acid. Commercially available acid anhydride hardeners include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" from New Japan Chemical Co., Ltd., "YH-306" and "YH-307" from Mitsubishi Chemical Co., Ltd., and "HN-2200" and "HN-5500" from Hitachi Chemical Co., Ltd.

[0082] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propanediamine, and the like. bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. The amine-based curing agent may be a commercially available product, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0083] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0084] The ratio of the amount of the (A) epoxy resin to the (B) curing agent is preferably 1:0.01 to 1:2, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:1.5, in terms of the ratio of [total number of epoxy groups in the epoxy resin] to [total number of reactive groups in the curing agent]. Here, the reactive groups in the (B) curing agent are active ester groups, active hydroxyl groups, etc., and vary depending on the type of the (B) curing agent. The total number of epoxy groups in the (A) epoxy resin is the total value of the non-volatile mass of each of the (A) epoxy resins divided by the epoxy equivalent, and the total number of reactive groups in the (B) curing agent is the total value of the non-volatile mass of each of the (B) curing agents divided by the reactive group equivalent, and ...

[0085] The content of the (B) component is preferably determined so as to satisfy the range of the ratio of the amount of the (A) epoxy resin to the (B) curing agent described above. From the viewpoint of enhancing the intended effect of the present invention, the content of the (B) component may be 0.5% by mass or more, 1% by mass or more, 2% by mass or more, or 3% by mass or more, and 50% by mass or less, 40% by mass or less, 30% by mass or less, or 25% by mass or less, when the non-volatile content in the resin composition is 100% by mass.

[0086] <(C) Inorganic filler> The resin composition may contain an inorganic filler (C). From the viewpoint of reducing the average linear thermal expansion coefficient of the cured product of the resin composition, it is preferable that the resin composition contains an inorganic filler.

[0087] The material of the inorganic filler is not particularly limited as long as it is an inorganic compound, and examples thereof include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium titanate zirconate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. As the silica, spherical silica is preferable. The inorganic filler may be used alone or in combination of two or more. Commercially available silica products include "SO-C2" and "SO-C1" manufactured by Admatechs Co., Ltd., and "UFP-30" and "UFP-40" manufactured by Denka Co., Ltd.

[0088] The average particle size of the inorganic filler is usually 20 μm or less, and from the viewpoint of enhancing the intended effect of the present invention, it is preferably 10 μm or less, more preferably 5.0 μm or less, even more preferably 2.5 μm or less, and even more preferably 2.0 μm or less. The lower limit of the average particle size is not particularly limited, but may be 1 nm (0.001 μm) or more, 5 nm or more, 10 nm or more, etc.

[0089] The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample is preferably one in which the inorganic filler is dispersed in methyl ethyl ketone using ultrasonic waves. Examples of the laser diffraction / scattering type particle size distribution measuring device that can be used include the "LA-500" manufactured by Horiba, Ltd. and the "SALD-2200" manufactured by Shimadzu Corporation.

[0090] From the viewpoint of improving embeddability, the inorganic filler is preferably treated with a surface treatment agent, more preferably with one or more surface treatment agents such as a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane compound, an organosilazane compound, a titanate coupling agent, etc., and even more preferably with an aminosilane silane coupling agent. The surface treatment agent preferably has a functional group that reacts with other components, such as a resin, such as an epoxy group, an amino group, or a mercapto group, and more preferably the functional group is bonded to the terminal group. Commercially available surface treatment agents include, for example, Shin-Etsu Chemical Co., Ltd.'s silane coupling agent "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s silane coupling agent "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s silane coupling agent "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s silane coupling agent "KBM573" (N-phenyl- ... Examples of suitable coupling agents include the silane coupling agent "KBM-4803" (long-chain epoxy type silane coupling agent), and the silane coupling agent "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., a silane coupling agent "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., an alkoxysilane compound "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., a silane coupling agent "KBM-4803" (long-chain epoxy type silane coupling agent), and the silane coupling agent "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.

[0091] With regard to the degree of surface treatment with the surface treatment agent, from the viewpoint of improving embeddability, etc., the surface treatment is preferably performed with 0.2 parts by mass to 5 parts by mass of the surface treatment agent per 100 parts by mass of component (C), more preferably with 0.2 parts by mass to 4 parts by mass, and even more preferably with 0.3 parts by mass to 3 parts by mass.

[0092] The degree of surface treatment with a surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving embeddability, the amount of carbon per unit surface area of ​​the inorganic filler is 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0093] The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the non-volatile components, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.

[0094] The specific surface area of ​​component (C) is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area is determined according to the BET method by adsorbing nitrogen gas onto the surface of the sample using a BET fully automatic specific surface area measuring device ("Macsorb HM-1210" manufactured by Mountech Co., Ltd.) and calculating the specific surface area using the BET multipoint method.

[0095] The content of the (C) component is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more or 71% by mass or more, when the nonvolatile content in the resin composition is 100% by mass, from the viewpoint of reducing the average linear thermal expansion coefficient of the cured product of the resin composition. The upper limit is not particularly limited, but is usually 95% by mass or less, and may be 94% by mass or less or 93% by mass or less. In the present invention, as illustrated in the examples, it has been confirmed that, when the nonvolatile content in the resin composition is 100% by mass, even if the content of the (C) component is 70% by mass or more, warping is suppressed and a cured product with excellent long-term reliability is obtained.

[0096] <(D) Thermoplastic resin> The resin composition may contain a thermoplastic resin (D) as an optional component. When the resin composition is in the form of a resin sheet or film, it is preferable that the resin composition contains the component (D). However, the value Z f As long as the content of the component (D) is within the specified range, the resin composition does not need to contain the component (D).

[0097] The polystyrene-equivalent weight average molecular weight (Mw) of the component (D) is preferably 1000 or more, more preferably 1500 or more, even more preferably 2000 or more, or 3000 or more. The upper limit is preferably 1,000,000 or less, more preferably 900,000 or less. The polystyrene-equivalent number average molecular weight (Mn) of the component (D) is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 2000 or more, or 3000 or more. The upper limit is preferably 1,000,000 or less, more preferably 900,000 or less. The polystyrene-equivalent weight average molecular weight (Mw) and number average molecular weight (Mn) of the component (D) are measured by gel permeation chromatography (GPC). Specifically, the polystyrene-equivalent weight average molecular weight (Mw) and number average molecular weight (Mn) of component (D) can be measured at a column temperature of 40°C using a measuring device LC-9A / RID-6A manufactured by Shimadzu Corporation, a column Shodex K-800P / K-804L / K-804L manufactured by Showa Denko KK, and chloroform or the like as a mobile phase, and calculated using a calibration curve of standard polystyrene.

[0098] (D) Examples of the thermoplastic resin include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetheretherketone resin, polyester resin, etc., and phenoxy resin is preferred. The thermoplastic resin may be used alone or in combination of two or more.

[0099] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more. Specific examples of phenoxy resins include "1256" and "4250" (both of which are phenoxy resins containing a bisphenol A skeleton), "YX8100" (phenoxy resin containing a bisphenol S skeleton), and "YX6954" (phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation. Other examples include "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd., and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0100] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., and S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0101] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0102] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0103] A specific example of polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. A specific example of polyphenylene ether resin is "OPE-2St 1200" oligophenylene ether-styrene resin manufactured by Mitsubishi Gas Chemical Co., Ltd. A specific example of polyetheretherketone resin is "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd. A specific example of polyetherimide resin is "Ultem" manufactured by GE Corporation.

[0104] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0105] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin-based elastomers such as polypropylene and ethylene-propylene block copolymer.

[0106] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0107] As the (D) component, a resin having one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule is preferable, a resin having one or more structures selected from a polybutadiene structure, a poly(meth)acrylate structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure is more preferable, and a resin having one or more structures selected from a polybutadiene structure and a polycarbonate structure is even more preferable. Note that "(meth)acrylate" is a term that includes methacrylate and acrylate, and combinations thereof. These structures may be included in the main chain or in the side chain.

[0108] Component (D) preferably has a reactive functional group (hereinafter also referred to as a "reactive functional group"), which allows it to be incorporated into the crosslinked structure formed by components (A) and (B). The reactive functional group may be one that exhibits reactivity upon heating or light irradiation.

[0109] Examples of reactive groups contained in the (D) component include hydroxyl, carboxyl, amino, vinyl, acryloyl, and methacryloyl groups. Instead of the vinyl group, a group having a carbon-carbon double bond may be used. The hydroxyl group is preferably a phenolic hydroxyl group from the viewpoint of increasing the heat resistance of the crosslinked structure.

[0110] A preferred embodiment of the component (D) is a resin containing a polybutadiene structure, and the polybutadiene structure may be contained in the main chain or in the side chain. The polybutadiene structure may be partially or entirely hydrogenated. A resin containing a polybutadiene structure is called a polybutadiene resin.

[0111] Specific examples of polybutadiene resins include "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", and "Ricon 184MA6" (polybutadiene containing an acid anhydride group) manufactured by Cray Valley Corporation; "GQ-1000" (polybutadiene having hydroxyl and carboxyl groups introduced therein), "G-1000", "G-2000", and "G-3000" (polybutadiene having hydroxyl groups at both ends), "GI-1000", "GI-2000", and "GI-3000" (polybutadiene having hydrogenated hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd.; and "FCA-061L" (hydrogenated polybutadiene skeleton epoxy resin) manufactured by Nagase ChemteX Corporation. Also, as the polybutadiene resin, a thermoplastic resin A having a reactive functional group contained in the thermoplastic resin solution A prepared in <Preparation of thermoplastic resin solution A> described later or a modified product thereof may be used. Also, as the polybutadiene resin, a resin having a residue obtained by removing the hydroxyl group of bifunctional hydroxyl group-terminated polybutadiene or a modified product thereof disclosed in JP 2006-37083 A may be used, and among these, from the viewpoint of obtaining a cured product having excellent flexibility, it is preferable to use a resin having a residue obtained by removing the hydroxyl group of bifunctional hydroxyl group-terminated polybutadiene having an average molecular weight of 800 to 1000 or a modified product thereof, or a resin having a polybutadiene structure content of 45 mass% or more or a modified product thereof. Furthermore, as the polybutadiene resin, a resin having a polybutadiene structure made from a polybutadiene polyol compound having two or more alcoholic hydroxyl groups in one molecule as disclosed in International Publication No. 2008 / 153208, or a modified product thereof, may be used. Of these, from the viewpoint of obtaining a cured product having excellent flexibility, it is preferable to use a resin having a polybutadiene structure made from a polybutadiene polyol compound having a number average molecular weight of 300 to 5000, or a modified product thereof.The content of butadiene structures in the polybutadiene resin is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, 65% by mass or more, or 70% by mass or more, and the upper limit of the content of butadiene structures is naturally determined by other structural portions in the molecule.

[0112] A preferred embodiment of the component (D) is a resin containing a poly(meth)acrylate structure. A resin containing a poly(meth)acrylate structure is called a poly(meth)acrylic resin. Examples of poly(meth)acrylic resins include Teisan Resin manufactured by Nagase ChemteX Corporation, and "ME-2000", "W-116.3", "W-197C", "KG-25", and "KG-3000" manufactured by Negami Chemical Industries, Ltd.

[0113] A preferred embodiment of the component (D) is a resin containing a polycarbonate structure. A resin containing a polycarbonate structure is called a polycarbonate resin. Examples of polycarbonate resins include "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd. In addition, as the polycarbonate resin, a thermoplastic resin B having a reactive functional group contained in the thermoplastic resin solution B prepared in <Preparation of thermoplastic resin solution B> described later or a modified product thereof may be used. In addition, as the polycarbonate resin, a resin having a residue obtained by removing the hydroxyl group of a polycarbonate diol disclosed in International Publication No. 2016 / 129541 or a modified product thereof may be used. Among these, from the viewpoint of obtaining a cured product excellent in flexibility and chemical resistance, it is preferable to use a resin having a residue obtained by removing the hydroxyl group of a polycarbonate diol having a hydroxyl group equivalent of 250 to 1250 or a modified product thereof. In addition, as the polycarbonate resin, a resin having a residue obtained by removing the hydroxyl group of a polycarbonate polyol or a modified product thereof may be used. The content of the carbonate structure in the polycarbonate resin is preferably 60% by mass or more, more preferably 65% ​​by mass or more, and even more preferably 75% by mass or more, and the upper limit of the content of the carbonate structure is naturally determined by other structural parts in the molecule.

[0114] Another embodiment of the component (D) is a resin containing a siloxane structure. A resin containing a siloxane structure is called a siloxane resin. Examples of siloxane resins include "SMP-2006", "SMP-2003PGMEA", and "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimides made from amine-terminated polysiloxane and tetrabasic acid anhydride (see WO 2010 / 053185, JP 2002-12667, JP 2000-319386, etc.).

[0115] Another embodiment of the component (D) is a resin containing an alkylene structure or an alkyleneoxy structure. A resin containing an alkylene structure is called an alkylene resin, and a resin containing an alkyleneoxy structure is called an alkyleneoxy resin. The polyalkyleneoxy structure is preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms, and even more preferably a polyalkyleneoxy structure having 5 to 6 carbon atoms. Specific examples of the alkylene resin and the alkyleneoxy resin include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation.

[0116] Another embodiment of the component (D) is a resin containing an isoprene structure. A resin containing an isoprene structure is called an isoprene resin. Specific examples of isoprene resins include "KL-610" and "KL613" manufactured by Kuraray Co., Ltd.

[0117] Another embodiment of the (D) component is a resin containing an isobutylene structure. A resin containing an isobutylene structure is called an isobutylene resin. Specific examples of isobutylene resins include "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer) manufactured by Kaneka Corporation.

[0118] The content of the (D) component may be 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more, when the resin component in the resin composition is 100% by mass. The lower limit is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, from the viewpoint of achieving the desired effect of including the (D) component. The upper limit is preferably 65% ​​by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less, from the viewpoint of obtaining a cured product with excellent long-term reliability. The resin component refers to all components contained in the resin composition excluding the (C) inorganic filler and (F) other additives.

[0119] The content of the (D) component may be 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more, assuming that the non-volatile components in the resin composition are 100% by mass. From the viewpoint of achieving the desired effect of including the (D) component, the lower limit is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. From the viewpoint of obtaining a cured product with excellent long-term reliability, the upper limit is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0120] <(E) Curing accelerator> The resin composition may contain (E) a curing accelerator. Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators are preferred, and amine-based curing accelerators are more preferred. The curing accelerator may be used alone or in combination of two or more.

[0121] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0122] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.

[0123] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.

[0124] As the imidazole-based curing accelerator, commercially available products may be used, for example, imidazole compound "1B2PZ" manufactured by Shikoku Kasei Corporation, "P200-H50" manufactured by Mitsubishi Chemical Corporation, and the like.

[0125] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0126] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0127] When the resin composition contains the (E) component, the content of the (E) component is usually 0.001% by mass or more, preferably 0.01% by mass or more, and more preferably 0.02% by mass or more, based on 100% by mass of the non-volatile content in the resin composition. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. This can reliably promote the curing of the resin composition.

[0128] <(F) Optional Additives> In one embodiment, the resin composition may further contain (F) other additives (excluding the components (A) to (E)), as necessary. Examples of such other additives include organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, as well as resin additives such as thickeners, defoamers, leveling agents, adhesion promoters, and colorants.

[0129] As the organic filler, any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, such as rubber particles, polyamide fine particles, silicone particles, etc. As the rubber particles, commercially available products may be used, such as "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.

[0130] The content of the (F) component is arbitrary as long as it does not excessively impair the intended effects of the present invention. When the non-volatile components in the resin composition are taken as 100% by mass, the content may be, for example, 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more, and may be, for example, 15% by mass or less, 13% by mass or less, or 10% by mass or less.

[0131] <Characteristics of resin composition> (Value Z f ) The resin composition of the present invention is cured at 180°C for 90 minutes to obtain a cured product, and the value Z obtained by dividing the average linear thermal expansion coefficient α by the crosslink density n is f (ppm cm 3 / mol K) is 145 <Z f <1300, and preferably 150≦Zf≦1000. As a result, as demonstrated in the Examples section, the resin composition of the present invention can provide a cured product that is less prone to warping and has excellent long-term reliability, as compared with the comparative examples. f is < value Z f The acquisition of the Z fis usually 145(ppm cm 3 / mol K), preferably 150 (ppm cm 3 / mol·K) or more, and from the viewpoint of enhancing the intended effects of the present invention (suppression of warping and long-term reliability), it is preferably 155 (ppm·cm 3 / mol K) or more, and more preferably 160 (ppm cm 3 / mol K) or more, usually 1300 (ppm cm 3 / mol K), preferably less than 1000 (ppm cm 3 / mol·K), and from the viewpoint of enhancing the intended effects of the present invention, it is preferably 700 (ppm·cm 3 / mol K) or less, and more preferably 500 (ppm cm 3 / mol K), where the value Z f The value Z can be adjusted, for example, by changing the types and amounts of the components (A) and (B) contained in the resin composition. f is a parameter expressed by a relational expression between the average linear thermal expansion coefficient α and the crosslink density n, and is a parameter related to suppression of warpage and long-term reliability. Therefore, it can be understood as one of the indexes that already reflects parameters related to (i) the presence or absence and content of component (C), which is a component that generally lowers the average linear thermal expansion coefficient α, (ii) the presence or absence and content of components or sites (e.g., components (C) and (D)) that can inhibit the formation of a crosslinked structure formed by an epoxy resin and a curing agent or suppress an increase in crosslink density, and (iii) the presence or absence and content of a component (e.g., component (E)) that can promote the formation of the crosslinked structure.

[0132] (glass transition temperature Tg) From the viewpoint of obtaining a cured product having excellent heat resistance, the resin composition of the present invention preferably has a glass transition temperature Tg (°C) of a cured product obtained by curing at 180°C for 90 minutes in the range of 150 to 240°C. The glass transition temperature Tg (°C) can be obtained during <Measurement of dynamic elastic modulus> described later. The glass transition temperature Tg (°C) is usually 150°C or higher, and from the viewpoint of obtaining a cured product having excellent heat resistance, it is preferably more than 165°C, more preferably 176°C or higher. The upper limit of the glass transition temperature Tg (°C) is usually 240°C or lower, but may be, for example, 210°C or lower, 209°C or lower, or 205°C or lower from the viewpoint of obtaining a cured product having excellent handleability.

[0133] (Average coefficient of linear thermal expansion α) From the viewpoint of enhancing the intended effect of the present invention, the resin composition of the present invention preferably has a small average linear thermal expansion coefficient α of the cured product obtained by curing at 180°C for 90 minutes. Here, the value of the average linear thermal expansion coefficient α can be adjusted to be lowered, for example, by adjusting the type and amount of the components such as the (A) component and the (B) component contained in the resin composition. The average linear thermal expansion coefficient α can be measured according to <Measurement of average linear thermal expansion coefficient (CTE) α> described later. The average linear thermal expansion coefficient α of such a cured product is usually less than 30 ppm / K, preferably 25 ppm / K or less, more preferably 20 ppm / K or less, and although there is no lower limit, it can be, for example, 1 ppm / K or more or 2 ppm / K or more. The average linear thermal expansion coefficient α of such a cured product is the above value Z f From the viewpoint of satisfying the above numerical range, it may be, for example, 5 ppm / K or more or 7 ppm / K or more.

[0134] (Storage modulus E' at a given temperature T (K)) The resin composition of the present invention has a storage modulus E' of typically 2.00×10 or less at a given temperature T (K) for a cured product obtained by curing at 180° C. for 90 minutes. 9The predetermined temperature T(K) is a temperature that indicates the sum of the glass transition temperature Tg(°C) of the cured product and 353(K) (i.e., a value obtained by adding 273K and then adding 80K to convert the glass transition temperature Tg(°C) into the unit K). Here, the value of the storage modulus E' at the predetermined temperature T(K) can be adjusted, for example, by the types and amounts of the components, such as the (A) component and the (B) component, contained in the resin composition. From the viewpoint of enhancing the intended effect of the present invention, the storage modulus E' is preferably 1.50×10 9 Pa or less, more preferably 1.40×10 9 Pa or less, more preferably 1.30×10 9 Pa or less or 1.20 x 10 9 Pa or less, typically 0.10×10 9 From the viewpoint of enhancing the intended effects of the present invention, the pressure drop is preferably 0.30×10 Pa or more. 9 Pa, more preferably 0.35×10 9 Pa or more, more preferably 0.40×10 9 Such a cured product has a viscosity of Z Pa or more. f From the viewpoint of satisfying the above-mentioned numerical range and enhancing the intended effect of the present invention, the average linear thermal expansion coefficient α is 25 ppm / K or less, and the storage modulus E' at a predetermined temperature T (K) is 1.50 × 10 9 Pa, or the average linear thermal expansion coefficient α is 25 ppm / K or less, and the storage modulus E' at a predetermined temperature T (K) is 0.30×10 9 It is preferable that the pressure exceeds 1 Pa. The predetermined temperature T(K) is within the range of 473K to 673K, for example.

[0135] (Crosslink density n) From the viewpoint of enhancing the intended effect of the present invention, the resin composition of the present invention is cured at 180° C. for 90 minutes to obtain a cured product having a crosslink density n of 0.15 mol / cm 3It is preferable that the crosslink density n is 0.15 mol / cm or less. Here, the value of the crosslink density n can be adjusted, for example, by the type and amount of the components, such as the (A) component and the (B) component, contained in the resin composition. The crosslink density n can be obtained by using the measurement results in <Measurement of dynamic elastic modulus> described later. From the viewpoint of enhancing the intended effect of the present invention, the crosslink density n is preferably 0.15 mol / cm or less. 3 Less than or equal to 0.15 mol / cm 3 More preferably, 0.15 mol / cm or less. 3 Less than or equal to 0.15 mol / cm 3 is usually 0.01 mol / cm or less. 3 From the viewpoint of enhancing the intended effects of the present invention, it is preferable that the concentration is 0.02 mol / cm 3 More preferably, 0.03 mol / cm 3 That's all.

[0136] The resin composition of the present invention can provide an insulating layer formed of a cured product with suppressed warping and excellent long-term reliability. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board), and can be more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board). In addition, since the resin composition of the present invention provides an insulating layer formed of a cured product with suppressed warping and excellent long-term reliability, it can be suitably used even when the printed wiring board is a circuit board with built-in components. Furthermore, since the resin composition of the present invention provides an insulating layer formed of a cured product with suppressed warping and excellent long-term reliability, it can be more suitably used as a resin composition for forming a solder resist layer (resin composition for forming a solder resist layer of a printed wiring board). In addition, since the resin composition of the present invention provides an insulating layer formed of a cured product with suppressed warping, it can be suitably used as a resin composition for forming an encapsulating layer for encapsulating a semiconductor chip for a semiconductor chip package (resin composition for forming an encapsulating layer of a semiconductor chip package). The resin composition of the present invention can also be suitably used as a resin composition for forming a rewiring formation layer for a semiconductor chip package (resin composition for forming a rewiring formation layer for a semiconductor chip package).

[0137] A semiconductor chip package including a rewiring formation layer is manufactured, for example, through the following steps (1) to (6). (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer. In addition, when a semiconductor chip package including an encapsulation layer is manufactured, a redistribution layer may be further formed on the encapsulation layer.

[0138] <Method of producing resin composition> The method for producing the resin composition of the present invention is not particularly limited, and examples thereof include a method in which the blending components are mixed with a solvent or the like as necessary and dispersed using a rotary mixer or the like. In producing the resin composition of the present invention, the above value Z can be obtained by selecting the components (A) and (B) and adjusting the content of the component (A) and the content of the component (B). f can be within the above range.

[0139] The resin composition can be obtained as a resin varnish by, for example, containing a solvent. In addition, from the viewpoint of achieving the intended effects of the present invention, it is preferable to dry the resin varnish and use the resin composition in a B-stage state or in the form of a film.

[0140] <Physical properties and applications of the cured resin composition> (Long-term reliability) The cured product obtained by thermally curing the resin composition of the present invention is usually excellent in long-term reliability. The long-term reliability can be evaluated according to the description in <Evaluation of Long-Term Reliability> described later. For example, it is preferable that the absolute value of the change in tensile strength at break before and after the HTS test is small (for example, less than 20% or 10% or less) for the cured product obtained by thermally curing the resin composition under conditions of 180°C for 90 minutes.

[0141] (Suppression of warpage) When the cured product obtained by thermally curing the resin composition of the present invention is formed on a substrate, the warping of the substrate is usually suppressed. The warping can be evaluated according to the description in <Evaluation of Warping> described later. For example, the maximum warping amount that can occur on a substrate on which a cured product having a thickness of 300 μm is formed by thermally curing the resin composition at 180° C. for 90 minutes can be 2000 μm or less.

[0142] (Chemical resistance) The cured product obtained by thermally curing the resin composition of the present invention usually exhibits excellent chemical resistance. The chemical resistance can be evaluated according to the description in <Evaluation of Chemical Resistance> described below. For example, a cured product having a thickness of 100 μm obtained by thermally curing the resin composition at 180° C. for 90 minutes can have a mass loss of 1% by mass or less before and after immersion in a strong alkaline aqueous solution (e.g., potassium hydroxide aqueous solution, tetramethylammonium hydroxide solution, sodium hydroxide aqueous solution, or sodium carbonate aqueous solution).

[0143] (glass transition temperature Tg) From the viewpoint of excellent heat resistance, the cured product obtained by thermally curing the resin composition of the present invention preferably has a glass transition temperature Tg (° C.) in the range of 150 to 240° C. More preferable ranges are as described above for the resin composition.

[0144] (Average coefficient of linear thermal expansion α) In order to enhance the intended effects of the present invention, it is preferable that the cured product obtained by thermally curing the resin composition of the present invention has a small average linear thermal expansion coefficient α. More preferable ranges are as described above for the resin composition.

[0145] (Storage modulus E' at a given temperature T (K)) The cured product obtained by thermally curing the resin composition of the present invention has a storage modulus E' at a given temperature T (K) of usually 2.00 × 10 9 The preferred range and the like are as described above for the resin composition.

[0146] (Crosslink density n) In order to enhance the intended effects of the present invention, the cured product obtained by thermally curing the resin composition of the present invention has a crosslink density n of 0.15 mol / cm 3 More preferred ranges and the like are as described above for the resin composition.

[0147] (Value Z f ) The cured product obtained by thermally curing the resin composition of the present invention has a value Z obtained by dividing the average linear thermal expansion coefficient α by the crosslink density n. f (ppm cm 3 / mol K) is 145 <Z f It is preferable that Zf < 1300 is satisfied, and more preferably 150 ≦ Zf ≦ 1000 is satisfied. As demonstrated in the Examples section, such a cured product has suppressed warpage and is excellent in long-term reliability. More preferable ranges etc. are as described above for the resin composition.

[0148] The cured product of the resin composition of the present invention has suppressed warping and is excellent in long-term reliability. Therefore, the cured product of the resin composition of the present invention can be suitably used as an insulating layer of a printed wiring board, and more suitably used as an interlayer insulating layer of a printed wiring board. In addition, the cured product of the resin composition of the present invention provides an insulating layer with suppressed warping and excellent long-term reliability, so it can be suitably used even when the printed wiring board is a circuit board with built-in components. Furthermore, the cured product of the resin composition of the present invention provides an insulating layer formed of a cured product with suppressed warping and excellent long-term reliability, so it can be more suitably used as a solder resist layer. In addition, the cured product of the resin composition of the present invention provides an insulating layer formed of a cured product with suppressed warping, so it can be suitably used as an encapsulating layer for encapsulating a semiconductor chip for a semiconductor chip package. In addition, the cured product of the resin composition of the present invention can be suitably used as a rewiring formation layer (insulating layer) for forming a rewiring layer of a semiconductor chip package.

[0149] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer containing the resin composition of the present invention provided on the support. The resin composition layer may be in a B-stage state.

[0150] The thickness of the resin composition layer of the resin sheet is usually 150 μm or less, preferably 110 μm or less, and may be 50 μm or less or 40 μm or less from the viewpoint of thinning the printed wiring board. The thickness may be further reduced. The lower limit of the thickness of the resin composition layer is not particularly limited, but may usually be 1 μm or more, 1.5 μm or more, 2 μm or more, etc.

[0151] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0152] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0153] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0154] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0155] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0156] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0157] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0158] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a support using a die coater or the like, and then drying the same to form a resin composition layer.

[0159] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0160] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0161] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0162] The resin sheet of the present invention provides an insulating layer formed of a cured product with suppressed warping and excellent long-term reliability. Therefore, the resin sheet of the present invention can be suitably used as a resin sheet for forming an insulating layer of a printed wiring board (resin sheet for forming an insulating layer of a printed wiring board), and can be more suitably used as a resin sheet for forming an interlayer insulating layer of a printed wiring board (resin sheet for forming an interlayer insulating layer of a printed wiring board). The resin sheet of the present invention can also be suitably used as a resin sheet for forming a solder resist layer of a printed wiring board (resin sheet for forming a solder resist layer of a printed wiring board). In addition, since the resin sheet of the present invention provides an insulating layer formed of a cured product with suppressed warping, it can also be suitably used as a resin composition for forming an encapsulating layer that encapsulates a semiconductor chip for a semiconductor chip package (resin sheet for forming an encapsulating layer of a semiconductor chip package). In addition, the resin sheet of the present invention can also be suitably used as a resin sheet for forming a rewiring formation layer (insulating layer) of a semiconductor chip package (resin sheet for forming a rewiring formation layer for a semiconductor chip package).

[0163] <Printed wiring board> The printed wiring board of the present invention includes an insulating layer formed containing a cured product of the resin composition of the present invention. The printed wiring board can be produced, for example, by a production method including the following steps (1) and (2). (1) A step of forming a resin composition layer containing a resin composition of the present invention on a substrate using the resin composition of the present invention. (2) A step of thermally curing the resin composition layer to form an insulating layer.

[0164] In step (1), a substrate is prepared. Examples of the substrate include glass epoxy substrates, metal substrates (such as stainless steel and cold-rolled steel sheet (SPCC)), polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. The substrate may have a metal layer such as copper foil on the surface as a part of the substrate. For example, a substrate having a peelable first metal layer and a peelable second metal layer on both surfaces may be used. When such a substrate is used, a conductor layer as a wiring layer that can function as a circuit wiring is usually formed on the surface of the second metal layer opposite to the first metal layer. Examples of substrates having such a metal layer include "Micro Thin", an ultra-thin copper foil with a carrier copper foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0165] A conductor layer may be formed on one or both surfaces of the substrate. In the following description, a member including a substrate and a conductor layer formed on the substrate surface may be referred to as a "substrate with wiring layer" as appropriate. Examples of the conductor material included in the conductor layer include materials including one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor material may be a single metal or an alloy. Examples of the alloy include alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). Among them, from the viewpoints of versatility, cost, and ease of patterning in the formation of the conductor layer, chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper as single metals; and alloys of nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy as alloys; are preferred. Among these, the single metals chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver and copper; and nickel-chromium alloys; are more preferable, and the single metal copper is particularly preferable.

[0166] The conductor layer may be patterned, for example, to function as a wiring layer. In this case, the line (circuit width) / space (width between circuits) ratio of the conductor layer is not particularly limited, but is preferably 20 / 20 μm or less (i.e., pitch is 40 μm or less), more preferably 10 / 10 μm or less, even more preferably 5 / 5 μm or less, even more preferably 1 / 1 μm or less, and particularly preferably 0.5 / 0.5 μm or more. The pitch does not need to be the same throughout the conductor layer. The minimum pitch of the conductor layer may be, for example, 40 μm or less, 36 μm or less, or 30 μm or less.

[0167] The thickness of the conductor layer depends on the design of the printed wiring board, but is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, and particularly preferably 15 μm to 20 μm.

[0168] The conductor layer can be formed, for example, by a method including a step of laminating a dry film (photosensitive resist film) on a substrate, a step of forming a pattern by exposing and developing the dry film under predetermined conditions using a photomask to obtain a patterned dry film, a step of forming a conductor layer by a plating method such as electrolytic plating using the developed patterned dry film as a plating mask, and a step of peeling off the patterned dry film. As the dry film, a photosensitive dry film made of a photoresist composition can be used, and for example, a dry film formed of a resin such as a novolac resin or an acrylic resin can be used. The lamination conditions of the substrate and the dry film can be the same as the lamination conditions of the substrate and the resin sheet described later. The peeling off of the dry film can be carried out using, for example, an alkaline peeling solution such as a sodium hydroxide solution.

[0169] After preparing the substrate, a resin composition layer is formed on the substrate. When a conductor layer is formed on the surface of the substrate, the resin composition layer is preferably formed so that the conductor layer is embedded in the resin composition layer.

[0170] The resin composition layer is formed, for example, by laminating a resin sheet and a substrate. This lamination can be performed, for example, by bonding the resin sheet to the substrate from the support side under heat and pressure, thereby laminating the resin composition layer to the substrate. Examples of the member for heat-pressing the resin sheet to the substrate (hereinafter, sometimes referred to as a "heat-pressing member") include a heated metal plate (such as a SUS plate) or a metal roll (such as a SUS roll). It is preferable to press the heat-pressing member through an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the substrate, rather than directly pressing the resin sheet.

[0171] The lamination of the substrate and the resin sheet may be carried out, for example, by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C. The thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa. The thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably carried out under reduced pressure conditions of a pressure of 13hPa or less.

[0172] After lamination, the laminated resin sheets may be smoothed under normal pressure (atmospheric pressure), for example, by pressing the support side with a thermocompression member. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The lamination and smoothing treatment may be performed successively using a vacuum laminator.

[0173] The resin composition layer can be formed, for example, by compression molding. The molding conditions may be the same as those of the method for forming the resin composition layer in the step of forming the sealing layer of the semiconductor chip package described later.

[0174] After forming the resin composition layer on the substrate, the resin composition layer is thermally cured to form an insulating layer. The thermal curing conditions for the resin composition layer vary depending on the type of resin composition, but the curing temperature is usually in the range of 120°C to 240°C (preferably in the range of 150°C to 220°C, more preferably in the range of 170°C to 200°C), and the curing time is in the range of 5 minutes to 120 minutes (preferably in the range of 10 minutes to 100 minutes, more preferably in the range of 15 minutes to 90 minutes).

[0175] Before the resin composition layer is thermally cured, the resin composition layer may be subjected to a preheating treatment at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of usually 50° C. or more and less than 120° C. (preferably 60° C. or more and 110° C. or less, more preferably 70° C. or more and 100° C. or less) for usually 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).

[0176] In the manner described above, a printed wiring board having an insulating layer can be manufactured. The method for manufacturing a printed wiring board may further include any optional step. For example, when a printed wiring board is manufactured using a resin sheet, the method for manufacturing a printed wiring board may include a step of peeling off the support of the resin sheet. The support may be peeled off before or after the resin composition layer is thermally cured.

[0177] The method for manufacturing a printed wiring board may include, for example, a step of polishing the surface of an insulating layer after forming the insulating layer. The polishing method is not particularly limited. For example, the surface of the insulating layer can be polished using a surface grinder.

[0178] The method for manufacturing a printed wiring board may include, for example, a step (3) of connecting the conductor layers to each other, for example, a step of drilling holes in the insulating layer. This allows holes such as via holes and through holes to be formed in the insulating layer. Examples of the method for forming the via holes include laser irradiation, etching, and mechanical drilling. The size and shape of the via holes may be appropriately determined depending on the design of the printed wiring board. In addition, the step (3) may also be performed by polishing or grinding the insulating layer to perform the interlayer connection.

[0179] After the via holes are formed, it is preferable to carry out a step of removing smears in the via holes. This step is sometimes called a desmear step. For example, when the conductive layer is formed on the insulating layer by a plating step, the via holes may be subjected to a wet desmear process. When the conductive layer is formed on the insulating layer by a sputtering step, a dry desmear process such as a plasma treatment process may be carried out. Furthermore, the insulating layer may be roughened by the desmear process.

[0180] Furthermore, before forming the conductor layer on the insulating layer, the insulating layer may be subjected to a roughening treatment. This roughening treatment usually roughens the surface of the insulating layer including the inside of the via hole. The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order.

[0181] After the via holes are formed, a conductor layer may be formed on the insulating layer. By forming a conductor layer at the position where the via holes are formed, the newly formed conductor layer and the conductor layer on the surface of the substrate are electrically connected to each other, and interlayer connection is performed. Examples of the method for forming the conductor layer include plating, sputtering, and vapor deposition, among which plating is preferred. In a preferred embodiment, the surface of the insulating layer is plated by an appropriate method such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. In addition, when the support in the resin sheet is a metal foil, a conductor layer having a desired wiring pattern can be formed by a subtractive method. The material of the conductor layer to be formed may be a single metal or an alloy. In addition, this conductor layer may have a single layer structure, or may have a multi-layer structure including two or more layers of different types of materials.

[0182] Here, an example of an embodiment in which a conductor layer is formed on an insulating layer will be described in detail. A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer, exposing a part of the plating seed layer corresponding to a desired wiring pattern. After forming an electrolytic plating layer on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by a process such as etching, and a conductor layer having a desired wiring pattern can be formed. Note that, when forming the conductor layer, the dry film used to form the mask pattern is the same as the above-mentioned dry film.

[0183] The method for producing a printed wiring board may include a step (4) of removing the substrate. By removing the substrate, a printed wiring board having an insulating layer and a conductor layer embedded in the insulating layer is obtained. This step (4) can be carried out, for example, when a substrate having a peelable metal layer is used.

[0184] <Semiconductor chip package> The semiconductor chip package according to the first embodiment of the present invention includes the above-mentioned printed wiring board and a semiconductor chip mounted on the printed wiring board. The semiconductor chip package can be manufactured by bonding the semiconductor chip to the printed wiring board.

[0185] The bonding conditions between the printed wiring board and the semiconductor chip may be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the printed wiring board. For example, the conditions used in flip-chip mounting of the semiconductor chip may be used. Also, for example, the semiconductor chip and the printed wiring board may be bonded via an insulating adhesive.

[0186] An example of a bonding method is a method in which a semiconductor chip is pressure-bonded to a printed wiring board. Pressure-bonding conditions are a pressure-bonding temperature usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and a pressure-bonding time usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).

[0187] Another example of the bonding method is a method of bonding a semiconductor chip to a printed wiring board by reflow. The reflow conditions may be in the range of 120°C to 300°C.

[0188] After the semiconductor chip is bonded to the printed wiring board, the semiconductor chip may be filled with a molded underfill material. As the molded underfill material, the above-mentioned resin composition or the above-mentioned resin sheet may be used.

[0189] The semiconductor chip package according to the second embodiment of the present invention includes a semiconductor chip and a cured product of the resin composition that encapsulates the semiconductor chip. In such a semiconductor chip package, the cured product of the resin composition usually functions as an encapsulation layer. An example of the semiconductor chip package according to the second embodiment is a fan-out type WLP.

[0190] The method for manufacturing such a semiconductor chip package includes: (A) a step of laminating a temporary fixing film on a substrate; (B) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (C) forming an encapsulation layer on the semiconductor chip; (D) peeling the substrate and the temporary fixing film from the semiconductor chip; (E) a step of forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; (F) forming a rewiring layer as a conductor layer on the rewiring formation layer; and (G) forming a solder resist layer on the rewiring layer; The method for manufacturing the semiconductor chip package may further include: (H) A process of dicing and separating multiple semiconductor chip packages into individual semiconductor chip packages. may also include

[0191] (Process (A)) Step (A) is a step of laminating a temporary fixing film on a substrate. The lamination conditions for the substrate and the temporary fixing film can be the same as the lamination conditions for the substrate and the resin sheet in the method for producing a printed wiring board.

[0192] Examples of the substrate include silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel (SPCC); substrates such as FR-4 substrates in which glass fibers are impregnated with epoxy resin or the like and then heat-cured; and substrates made of bismaleimide triazine resins such as BT resin.

[0193] The temporary fixing film may be made of any material that can be peeled off from the semiconductor chip and can temporarily fix the semiconductor chip. Commercially available products include "Riva Alpha" manufactured by Nitto Denko Corporation.

[0194] (Process (B)) Step (B) is a step of temporarily fixing the semiconductor chip on the temporary fixing film. The temporary fixing of the semiconductor chip can be performed using, for example, a device such as a flip chip bonder or a die bonder. The layout and number of the semiconductor chips can be appropriately set depending on the shape and size of the temporary fixing film, the number of semiconductor chip packages to be produced, etc. For example, the semiconductor chips may be temporarily fixed by arranging them in a matrix shape of multiple rows and multiple columns.

[0195] (Process (C)) Step (C) is a step of forming an encapsulating layer on the semiconductor chip. The encapsulating layer is formed by a cured product of the above-mentioned resin composition. The encapsulating layer is usually formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of thermally curing the resin composition layer to form the encapsulating layer.

[0196] The resin composition layer is preferably formed by a compression molding method, in which a semiconductor chip and a resin composition are usually placed in a mold, and pressure and, if necessary, heat are applied to the resin composition in the mold to form a resin composition layer covering the semiconductor chip.

[0197] A specific operation of the compression molding method can be, for example, as follows. An upper mold and a lower mold are prepared as molds for compression molding. A resin composition is applied to the semiconductor chip temporarily fixed on the temporary fixing film as described above. The semiconductor chip to which the resin composition is applied is attached to the lower mold together with the substrate and the temporary fixing film. Then, the upper mold and the lower mold are clamped, and heat and pressure are applied to the resin composition to perform compression molding.

[0198] In addition, the specific operation of the compression molding method may be, for example, as follows. An upper mold and a lower mold are prepared as molds for compression molding. A resin composition is placed on the lower mold. Also, a semiconductor chip is attached to the upper mold together with a substrate and a temporary fixing film. Thereafter, the upper mold and the lower mold are clamped so that the resin composition placed on the lower mold contacts the semiconductor chip attached to the upper mold, and heat and pressure are applied to perform compression molding.

[0199] The molding conditions vary depending on the composition of the resin composition, and appropriate conditions can be adopted so that good sealing is achieved. For example, the temperature of the mold during molding is preferably 70°C or higher, more preferably 80°C or higher, particularly preferably 90°C or higher, and preferably 200°C or lower, more preferably 170°C or lower, particularly preferably 150°C or lower. The pressure applied during molding is preferably 1 MPa or higher, more preferably 3 MPa or higher, particularly preferably 5 MPa or higher, preferably 50 MPa or lower, more preferably 30 MPa or lower, particularly preferably 20 MPa or lower. The cure time is preferably 1 minute or higher, more preferably 2 minutes or higher, particularly preferably 3 minutes or higher, preferably 60 minutes or lower, more preferably 30 minutes or lower, particularly preferably 20 minutes or lower. Usually, the mold is removed after the formation of the resin composition layer. The mold may be removed before or after the resin composition layer is thermally cured.

[0200] The resin composition layer may be formed by laminating a resin sheet and a semiconductor chip. For example, the resin composition layer of the resin sheet and the semiconductor chip are heated and pressed to form a resin composition layer on the semiconductor chip. The lamination of the resin sheet and the semiconductor chip is usually performed in the same manner as the lamination of the resin sheet and the substrate in the method for producing a printed wiring board, using a semiconductor chip instead of a substrate.

[0201] After forming a resin composition layer on the semiconductor chip, the resin composition layer is thermally cured to obtain an encapsulation layer that covers the semiconductor chip. This encapsulates the semiconductor chip with a cured product of the resin composition. The thermal curing conditions of the resin composition layer may be the same as the thermal curing conditions of the resin composition layer in the method for producing a printed wiring board. Furthermore, before thermally curing the resin composition layer, a preheating treatment may be performed on the resin composition layer at a temperature lower than the curing temperature. The treatment conditions of this preheating treatment may be the same as the preheating treatment in the method for producing a printed wiring board.

[0202] (Process (D)) Step (D) is a step of peeling off the substrate and the temporary fixing film from the semiconductor chip. It is desirable to adopt an appropriate peeling method according to the material of the temporary fixing film. For example, the peeling method may be a method of heating, foaming or expanding the temporary fixing film to peel it off. In addition, for example, the peeling method may be a method of irradiating the temporary fixing film with ultraviolet light through the substrate to reduce the adhesive strength of the temporary fixing film to peel it off.

[0203] In the method of peeling off the temporary fixing film by heating, foaming or expanding it, the heating conditions are usually 100° C. to 250° C. for 1 second to 90 seconds or 5 minutes to 15 minutes. In the method of peeling off the temporary fixing film by reducing the adhesive strength of the temporary fixing film by irradiating it with ultraviolet light, the irradiation amount of ultraviolet light is usually 10 mJ / cm 2 ~1000mJ / cm 2 It is.

[0204] (Process (E)) Step (E) is a step of forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off.

[0205] The material of the rewiring formation layer can be any material having insulating properties. Among them, photosensitive resins and thermosetting resins are preferred from the viewpoint of ease of manufacturing the semiconductor chip package. The resin composition of the present invention may be used as the thermosetting resin.

[0206] After forming the rewiring formation layer, via holes may be formed in the rewiring formation layer to provide interlayer connection between the semiconductor chip and the rewiring layer.

[0207] In the method of forming a via hole when the material of the rewiring formation layer is a photosensitive resin, the surface of the rewiring formation layer is usually irradiated with active energy rays through a mask pattern to photocure the rewiring formation layer in the irradiated portion. Examples of active energy rays include ultraviolet rays, visible rays, electron beams, X-rays, etc., and ultraviolet rays are particularly preferred. The irradiation amount and irradiation time of the ultraviolet rays can be appropriately set according to the photosensitive resin. Examples of the exposure method include a contact exposure method in which a mask pattern is attached to the rewiring formation layer and exposed, and a non-contact exposure method in which a mask pattern is not attached to the rewiring formation layer and exposed using parallel rays.

[0208] After the rewiring formation layer is photocured, the rewiring formation layer is developed to remove the unexposed portion to form a via hole. The development may be performed by either wet development or dry development. Examples of the development method include a dip method, a paddle method, a spray method, a brushing method, and a scraping method, and the paddle method is preferable from the viewpoint of resolution.

[0209] When the material of the rewiring formation layer is a thermosetting resin, the method of forming the via hole may be, for example, laser irradiation, etching, mechanical drilling, etc. Among them, laser irradiation is preferable. The laser irradiation can be performed using an appropriate laser processing machine using a light source such as a carbon dioxide laser, a UV-YAG laser, or an excimer laser.

[0210] The shape of the via hole is not particularly limited, but is generally circular (approximately circular). The top diameter of the via hole is preferably 50 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less. Here, the top diameter of the via hole refers to the diameter of the opening of the via hole on the surface of the rewiring formation layer.

[0211] (Process (F)) Step (F) is a step of forming a rewiring layer as a conductor layer on the rewiring formation layer. The method of forming the rewiring layer on the rewiring formation layer can be the same as the method of forming a conductor layer on an insulating layer in the method of manufacturing a printed wiring board. Steps (E) and (F) may be repeated to alternately stack (build up) the rewiring layers and the rewiring formation layers.

[0212] (Process (G)) Step (G) is a step of forming a solder resist layer on the rewiring layer. Any material having insulating properties can be used as the material of the solder resist layer. Among them, photosensitive resins and thermosetting resins are preferred from the viewpoint of ease of manufacturing the semiconductor chip package. The resin composition of the present invention may be used as the thermosetting resin.

[0213] In step (G), bumping processing may be performed to form bumps, if necessary. The bumping processing can be performed by a method such as solder balls or solder plating. In addition, the formation of via holes in the bumping processing can be performed in the same manner as in step (E).

[0214] (Process (H)) The method for manufacturing a semiconductor chip package may include a step (H) in addition to the steps (A) to (G). The step (H) is a step of dicing a plurality of semiconductor chip packages into individual semiconductor chip packages to separate them. The method for dicing the semiconductor chip packages into individual semiconductor chip packages is not particularly limited.

[0215] <Semiconductor device> The semiconductor device includes a semiconductor chip package. Examples of the semiconductor device include various semiconductor devices used in electrical products (e.g., computers, mobile phones, smartphones, tablet devices, wearable devices, digital cameras, medical devices, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0216] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were performed in an environment of normal temperature and pressure, unless otherwise specified.

[0217] <Preparation of Thermoplastic Resin Solution A> In a reaction vessel, 69 g of bifunctional hydroxyl-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight: 3000, hydroxyl group equivalent: 1800 g / eq.), 40 g of aromatic hydrocarbon mixed solvent ("IPZOL 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were placed and mixed to dissolve uniformly. This resulted in a solution. The solution was heated to 60°C, and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate group equivalent: 113 g / eq.) was added while further stirring, and the reaction was carried out for about 3 hours. This resulted in a first reaction solution.

[0218] Next, 23 g of cresol novolac resin (DIC "KA-1160", hydroxyl equivalent: 117 g / eq.) and 60 g of ethyl diglycol acetate (Daicel) were added to the first reaction solution, and the mixture was heated to 150° C. with stirring and reacted for about 10 hours. As a result, a second reaction solution was obtained. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the temperature of the second reaction solution was lowered to room temperature. The second reaction solution was then filtered through a 100-mesh filter cloth. As a result, a solution containing thermoplastic resin A (phenolic hydroxyl group-containing polybutadiene resin) having reactive functional groups as a non-volatile component (non-volatile component 50% by mass; hereinafter referred to as "thermoplastic resin solution A") was obtained as the filtrate. The number average molecular weight of thermoplastic resin A was 5900, and the glass transition temperature was -7°C.

[0219] <Preparation of Thermoplastic Resin Solution B> A flask equipped with a stirrer, a thermometer, and a condenser was charged with 368.41 g of ethyl diglycol acetate and 368.41 g of ExxonMobil's "Solvesso 150 (registered trademark)" (aromatic solvent). In addition, 100.1 g (0.4 mol) of diphenylmethane diisocyanate and 400 g (0.2 mol) of polycarbonate diol (Kuraray's "C-2015N", number average molecular weight: about 2000, hydroxyl equivalent: 1000 g / eq., non-volatile component: 100% by mass) were charged into the flask, and the reaction was carried out at 70° C. for 4 hours. This resulted in a first reaction solution.

[0220] Next, 195.9 g (0.2 mol) of nonylphenol novolac resin (hydroxyl equivalent: 229.4 g / eq, average 4.27 functional groups, average calculated molecular weight: 979.5 g / mol) and 41.0 g (0.1 mol) of ethylene glycol bisanhydrotrimellitate were further charged into the flask, and the temperature was raised to 150° C. over 2 hours, and the reaction was carried out for 12 hours. This resulted in a second reaction solution. -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was regarded as the end point of the reaction, and the temperature of the second reaction solution was lowered to room temperature. The second reaction solution was then filtered through a 100-mesh filter cloth. As a result, a solution containing thermoplastic resin B (phenolic hydroxyl group-containing polycarbonate resin) having reactive functional groups as a non-volatile component (non-volatile component 50% by mass; hereinafter, referred to as "thermoplastic resin solution B") was obtained as the filtrate. The number average molecular weight of thermoplastic resin B was 6100, and the glass transition temperature was 5°C.

[0221] [Example 1] <Preparation of Resin Varnish A> Bisphenol A type epoxy resin as component (A) ("jER828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 184-194 g / eq.) 3 parts, biphenyl type epoxy resin as component (A) ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 276 g / eq.) 1 part, glycidylamine type epoxy resin as component (A) ("630" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 95 g / eq.) 2 parts, cresol novolac resin as component (B-2) ("KA-1160" manufactured by DIC Corporation, phenolic hydroxyl group equivalent: 117 g / eq.) 2 parts, (B-2) 1.54 parts of active ester resin (DIC Corporation, "HPC-8000-65T", active group equivalent: about 223, toluene solution with 65% by mass of non-volatile components) as a component, 4 parts of maleimide compound (Designer Molecules' "BMI-689") as a component (B-1), 70 parts of inorganic filler A as a component (C), 20 parts of thermoplastic resin solution A (non-volatile components: 50%) as a component (D), 0.05 parts of curing accelerator (Shikoku Chemical Industry Co., Ltd., "1B2PZ") as a component (E), and 15 parts of methyl ethyl ketone as a solvent were mixed and uniformly dispersed in a high-speed rotating mixer. In this way, a resin varnish was prepared. Hereinafter, the resin varnishes prepared in this way are also collectively referred to as "resin varnish A".

[0222] Here, the inorganic filler A is spherical silica (manufactured by Admatechs Co., Ltd., "SO-C2") that has been surface-treated with an aminosilane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM573"). The average particle size was measured to be 0.5 μm, and the specific surface area was measured to be 5.8 m. 2 / g.

[0223] <Preparation of Resin Sheet B> As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Inc.; thickness: 38 μm, softening point: 130°C; hereinafter sometimes referred to as "release PET") was prepared, one of whose main surfaces had been release-treated with an alkyd resin-based release agent ("AL-5" manufactured by Lintec Corporation).

[0224] Resin varnish A was uniformly applied to the release-treated surface of release PET using a die coater so that the thickness of the resin composition layer after drying was 100 μm. Resin varnish A was then dried at 80° C. to 120° C. (average 100° C.) for 6 minutes. This resulted in a resin sheet including a support and a resin composition layer including a resin composition provided on the support. Hereinafter, the resin sheet thus produced is also collectively referred to as "resin sheet B."

[0225] <Preparation of Cured Product C for Evaluation> A part of the resin sheet B was cut out and heated at 180° C. for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product for evaluation. Hereinafter, the cured products for evaluation thus produced are collectively referred to as “cured product for evaluation C.”

[0226] <Acquisition and evaluation of various parameters of the cured product of the resin composition> Various parameters were obtained for the cured product of the resin composition using the resin sheet B or the cured product for evaluation C, and the cured product of the resin composition was evaluated in terms of warpage and long-term reliability according to the evaluation method described later. Furthermore, the cured product for evaluation C was evaluated in terms of chemical resistance according to the evaluation method described later.

[0227] [Example 2] In Example 1, 70 parts of inorganic filler A as component (A) was changed to 115 parts of inorganic filler B. Here, inorganic filler B was a spherical alumina treated with "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and had a maximum cut diameter of 5 μm. Measurements showed that inorganic filler B had an average particle size of 1.5 μm and a specific surface area of ​​2.0 m. 2 / g. Except for the above, a resin varnish A containing a resin composition was prepared in the same manner as in Example 1. Then, a resin sheet B and a cured product C for evaluation were obtained using the resin varnish A in the same manner as in Example 1, and the cured product of the resin composition was evaluated in the same manner as in Example 1 using the resin composition layer of the resin sheet B and the cured product C for evaluation.

[0228] [Example 3] In Example 1, 3 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation), 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd.), and 2 parts of glycidylamine type epoxy resin ("630" manufactured by Mitsubishi Chemical Corporation) as component (A) were changed to 2 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 184 to 194 g / eq.), 2 parts of naphthalene type epoxy resin ("HP4032" manufactured by DIC Corporation, epoxy equivalent: 135 to 165 g / eq.), and 2 parts of biphenyl type epoxy resin ("YX4000" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 185 g / eq.). Furthermore, in Example 1, 2 parts of cresol novolak resin ("KA-1160" manufactured by DIC Corporation) as component (B-2), 1.54 parts of active ester resin ("HPC-8000-65T" manufactured by DIC Corporation) as component (B-2), and 4 parts of maleimide compound ("BMI-689" manufactured by Designer Molecules) as component (B-1) were changed to 1 part of cresol novolak resin ("KA-1160" manufactured by DIC Corporation) as component (B-2) and 4 parts of maleimide compound ("BMI-689" manufactured by Designer Molecules) as component (B-1). Furthermore, in Example 1, 20 parts of thermoplastic resin solution A (non-volatile component: 50%) as component (D) was changed to 12 parts of thermoplastic resin solution A (non-volatile component: 50%) as component (D) and 12 parts of thermoplastic resin solution B (non-volatile component: 50%) as component (D). Also, in Example 1, 0.05 parts of a curing accelerator (manufactured by Shikoku Chemical Industry Co., Ltd., "1B2PZ") as component (E) was changed to 0.05 parts of a curing accelerator (4-dimethylaminopyridine (DMAP)) as component (E). Except for the above, a resin varnish A containing a resin composition was prepared in the same manner as in Example 1. Then, a resin sheet B and a cured product C for evaluation were obtained using the resin varnish A in the same manner as in Example 1, and the cured product of the resin composition was evaluated in the same manner as in Example 1 using the resin composition layer of the resin sheet B and the cured product C for evaluation.

[0229] [Comparative Example 1] In Example 1, 3 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation), 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd.), and 2 parts of glycidylamine type epoxy resin ("630" manufactured by Mitsubishi Chemical Corporation) as the component (A) were changed to 1 part of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 184 to 194 g / eq.), 6 parts of naphthalene type epoxy resin ("HP4032" manufactured by DIC Corporation, epoxy equivalent: 135 to 165 g / eq.), and 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 276 g / eq.). Furthermore, in Example 1, 2 parts of the cresol novolak resin (DIC Corporation, "KA-1160") as the component (B-2), 1.54 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2), and 4 parts of the maleimide compound (Designer Molecules Corporation, "BMI-689") as the component (B-1) were changed to 4.62 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2). The component (B-1) was not used. Furthermore, in Example 1, 70 parts of inorganic filler A as component (C) was changed to 60 parts of inorganic filler A. Furthermore, in Example 1, 20 parts of thermoplastic resin solution A (non-volatile component: 50%) as component (D) was changed to 16 parts of thermoplastic resin solution B (non-volatile component: 50%) as component (D). Furthermore, in Example 1, 0.05 parts of curing accelerator (manufactured by Shikoku Chemical Industry Co., Ltd., "1B2PZ") as component (E) was changed to 0.10 parts of curing accelerator (manufactured by Shikoku Chemical Industry Co., Ltd., "1B2PZ"). Except for the above, a resin varnish A containing a resin composition was prepared in the same manner as in Example 1. Then, a resin sheet B and a cured product C for evaluation were obtained using the resin varnish A in the same manner as in Example 1, and the cured product of the resin composition was evaluated in the same manner as in Example 1 using the resin composition layer of the resin sheet B and the cured product C for evaluation.

[0230] [Comparative Example 2] In Example 1, 3 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation), 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd.), and 2 parts of glycidylamine type epoxy resin ("630" manufactured by Mitsubishi Chemical Corporation) as component (A) were changed to 1 part of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 184 to 194 g / eq.), 4 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 276 g / eq.), and 2 parts of biphenyl type epoxy resin ("YX4000" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: about 185 g / eq.). Furthermore, in Example 1, 2 parts of the cresol novolac resin (DIC Corporation, "KA-1160", phenolic hydroxyl equivalent: 117g / eq.) as the component (B-2), 1.54 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2), and 4 parts of the maleimide compound (Designer Molecules Corporation, "BMI-689") as the component (B-1) were changed to 2 parts of the cresol novolac resin (DIC Corporation, "KA-1160", phenolic hydroxyl equivalent: 117g / eq.) as the component (B-2) and 6.16 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2). The component (B-1) was not used. Furthermore, in Example 1, 70 parts of inorganic filler A as component (C) was changed to 50 parts of inorganic filler A. Furthermore, in Example 1, 5.71 parts of epoxy group-containing phenoxy resin (manufactured by Mitsubishi Chemical Corporation, "YX7200B35", epoxy equivalent: 3000 to 16000 g / eq., non-volatile component: 35%) was used in place of 20 parts of thermoplastic resin solution A as component (D) (non-volatile component: 50%). In Example 1, 0.05 parts of curing accelerator (manufactured by Shikoku Chemical Industry Co., Ltd., "1B2PZ") as component (E) was changed to 0.10 parts of curing accelerator (manufactured by Shikoku Chemical Industry Co., Ltd., "1B2PZ"). Except for the above, a resin varnish A containing a resin composition was prepared in the same manner as in Example 1. Then, a resin sheet B and a cured product C for evaluation were obtained using the resin varnish A in the same manner as in Example 1, and the cured product of the resin composition was evaluated in the same manner as in Example 1 using the resin composition layer of the resin sheet B and the cured product C for evaluation.

[0231] [Comparative Example 3] In Example 1, 3 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation), 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd.), and 2 parts of glycidylamine type epoxy resin ("jER630" manufactured by Mitsubishi Chemical Corporation) as the component (A) were changed to 2 parts of bisphenol A type epoxy resin ("jER828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 184 to 194 g / eq.), 1 part of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 276 g / eq.), and 1 part of glycidylamine type epoxy resin ("630" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 95 g / eq.). Furthermore, in Example 1, 2 parts of the cresol novolac resin (DIC Corporation, "KA-1160") as the component (B-2), 1.54 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2), and 4 parts of the maleimide compound (Designer Molecules, "BMI-689") as the component (B-1) were changed to 2 parts of the cresol novolac resin (DIC Corporation, "KA-1160", phenolic hydroxyl equivalent: 117g / eq.) as the component (B-2) and 1.54 parts of the active ester resin (DIC Corporation, "HPC-8000-65T") as the component (B-2). The component (B-1) was not used. Furthermore, in Example 1, 70 parts of inorganic filler A as component (C) was changed to 40 parts of inorganic filler A. Furthermore, in Example 1, 20 parts of thermoplastic resin solution A (non-volatile component: 50%) as component (D) was changed to 32 parts of thermoplastic resin solution A (non-volatile component: 50%). Except for the above, a resin varnish A containing a resin composition was prepared in the same manner as in Example 1. Then, a resin sheet B and a cured product C for evaluation were obtained using the resin varnish A in the same manner as in Example 1, and the cured product of the resin composition was evaluated in the same manner as in Example 1 using the resin composition layer of the resin sheet B and the cured product C for evaluation.

[0232] [Evaluation method] Using the resin composition layer of the resin sheet B obtained in the above-mentioned Examples and Comparative Examples or the cured product C for evaluation, various parameters were obtained for the cured product of the resin composition, and the cured product was evaluated by the following method from the viewpoints of heat resistance, warpage, and long-term reliability. Furthermore, using the cured product C for evaluation, the cured product was evaluated by the following method from the viewpoint of chemical resistance. Table 1 lists the parameters used in the evaluation among the obtained parameters. The evaluation results are also shown in Table 1.

[0233] <Getting various parameters> (Measurement of average coefficient of linear thermal expansion (CTE) α) The cured product C for evaluation was cut to a width of about 5 mm and a length of about 15 mm to obtain a test piece D. A thermomechanical analysis was performed on the test piece D by a tensile load method using a thermomechanical analyzer (Rigaku's "Thermo Plus TMA8310"). In detail, after the test piece D was mounted on the thermomechanical analyzer, the thermal expansion coefficient was measured twice consecutively under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. Then, based on the result of the second measurement, the average linear thermal expansion coefficient α (ppm / K) in the range from 25°C (298K) to 150°C (423K) was calculated.

[0234] (Measurement of dynamic elastic modulus; Obtaining glass transition temperature Tg, storage modulus E' and crosslink density n) The cured product C for evaluation was cut to a width of 5 mm and a length of 15 mm to obtain a test piece E. A thermomechanical analysis was performed on this test piece E by a tensile load method using a viscoelasticity measuring device ("DMA7100" manufactured by Hitachi High-Tech Science Corporation). Specifically, after the test piece E was mounted on the thermomechanical analyzer, the storage modulus and loss modulus were measured under the measurement conditions of a load of 200 mN and a heating rate of 5° C. / min.

[0235] First, the glass transition temperature Tg (° C.) was obtained from the peak top of tan δ (temperature-dependent curve of the ratio of storage modulus and loss modulus) obtained as a measurement result.

[0236] Next, the predetermined temperature T(K) was determined. Specifically, the predetermined temperature T(K) was determined by adding 273K and then 80K to the obtained glass transition temperature Tg(°C) in order to convert it into the unit K. Note that, since the value of the storage modulus tends not to vary significantly in the temperature region near the predetermined temperature T(K), it is acceptable for the determined predetermined temperature T(K) to have an error within the range of -5°C to +5°C. Then, the measured value E' (unit: GPa, i.e., 10 9 Pa) was obtained.

[0237] Next, the crosslink density n (mol / cm) was calculated by substituting the obtained storage modulus E' (Pa) into the following equation: 3 Here, the crosslink density n can be considered as an index showing the number of crosslinked molecules present per unit volume. n=E' / 3RT (In the above formula, T is a given temperature T (K), E' is the measured storage modulus (Pa) at the given temperature T (K), and R is the gas constant of 8,310,000 (Pa cm 3 / mol K). E' / 3 is the measured value of the shear modulus G' at a given temperature T (K) (10 9 Pa) may also be used.

[0238] (Value Z f (Acquisition of Value Z f The average linear thermal expansion coefficient α (ppm / K) of the cured product is expressed as the crosslink density n (mol / cm 3 ) and this value Z f (ppm cm 3 / mol·K) was obtained as a parameter of the cured resin composition. fThe scope in which the problems of the present invention can be solved was examined by comparing the above with the evaluation results of each evaluation described below.

[0239] <Evaluation of long-term reliability> The long-term reliability was evaluated by subjecting the cured resin composition to an HTS test, measuring the strength at break before and after the HTS test, and calculating the degree of change (%) in the strength at break.

[0240] (HTS Testing) The cured product C for evaluation was subjected to an HTS test (High Thermal Storage test). In the HTS test, the cured product C for evaluation was kept at 150° C. for 1000 hours. As a result, a cured product C' for evaluation after the HTS test was obtained.

[0241] (Measurement of breaking strength before and after HTS test) The cured product C for evaluation was cut into a dumbbell-shaped No. 1 shape in plan view to obtain five test pieces F. Similarly, the cured product C' for evaluation was cut into a dumbbell-shaped No. 1 shape in plan view to obtain five test pieces F'. A tensile test was performed on each of the test pieces F and F' using an Orientec tensile tester "RTC-1250A" at 23°C and a test speed of 5mm / min, and the tensile strength at break (hereinafter also simply referred to as "break strength") was obtained from the stress-strain curve. The measurement was performed in accordance with JIS K7127:1999. The average value of the break strength of the five test pieces F was taken as the tensile strength at break σ0 before the HTS test. The average value of the break strength of the five test pieces F' was taken as the tensile strength at break σ1 after the HTS test. (Calculation of change rate (%)) Next, the degree of change (%) in the tensile strength at break before and after the HTS test was calculated based on the following formula. Degree of change (%) = {(σ1-σ0) / σ0} x 100 (evaluation) The degree of change (%) obtained as described above was evaluated according to the following criteria. "○": If the degree of change (%) is within the range of -10% to +10%, the degree of change is small and the long-term reliability is excellent. "X": The degree of change (%) is not within the range of -10% to +10%, the degree of change is large, and long-term reliability is poor. Moreover, when the test piece F' of Comparative Example 3, which was evaluated as having poor long-term reliability, was observed, degradation due to oxidation was found.

[0242] <Warpage evaluation> (Preparation of silicon wafers with insulating layers for warpage measurement) Resin sheet B was laminated on one entire surface of a 12-inch disk-shaped silicon wafer (thickness 775 μm) using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was bonded, and then the support was peeled off. On the resin composition layer laminated on the silicon wafer, the lamination of the resin sheet and the peeling of the support were repeated twice in the same procedure. As a result, a resin composition layer laminate having a thickness of 300 μm and consisting of a total of three resin composition layers was formed on the silicon wafer. The obtained silicon wafer with the resin composition layer laminate was heat-treated in an oven under conditions of 180° C. and 90 minutes. As a result, a silicon wafer with a resin composition layer in which curing had progressed (i.e., a silicon wafer with an insulating layer) was obtained. (Warpage measurement) With one end of the obtained silicon wafer with an insulating layer pressed against a flat table, the vertical distance between the lower surface of the end of the silicon wafer with an insulating layer and the upper surface of the table was measured as the amount of warping, and the end showing the maximum amount of warping (μm) was identified. (evaluation) The maximum warpage (μm) specified as described above was evaluated according to the following criteria. "○": If the maximum warpage is within the range of 0 μm to 2000 μm, the warpage is small and sufficiently suppressed. "X": If the maximum warpage exceeds 2000 μm, the warpage is large and not sufficiently suppressed.

[0243] <Evaluation of chemical resistance> (Chemical immersion test) The cured product C for evaluation was cut into squares with sides of 5 cm to obtain a plurality of test pieces G. The test pieces G were immersed in a strong alkaline aqueous solution at 70°C for 1 hour. A 1% by mass aqueous solution of potassium hydroxide was used as the strong alkaline aqueous solution. Thereafter, the test pieces G were taken out, washed with distilled water, and dried in an oven at 130°C for 1 hour. This resulted in the test pieces G' after the chemical immersion test.

[0244] (Measurement of mass before and after chemical immersion test and calculation of mass loss rate) The mass of the test piece G was measured and designated as the mass M0 before the chemical immersion test. The mass of the test piece G' was measured and designated as the mass M1 before the chemical immersion test. Next, the mass loss rate (%) before and after the chemical immersion test was calculated based on the following formula. Mass reduction rate (%)={(M0-M1) / M0}×100 (evaluation) The mass reduction rate (%) obtained as described above was evaluated according to the following criteria. "○": When the mass loss rate (%) is less than 1% by mass, the portion dissolved in chemicals is sufficiently small, and chemical resistance is excellent. "X": When the mass loss rate (%) is 1% by mass or more, a large portion has dissolved in the chemical, and the chemical resistance is poor.

[0245] [result] The results of the above-mentioned Examples and Comparative Examples are shown in Table 1 below. In Table 1 below, the amount of each component is expressed as the amount converted into non-volatile components. Furthermore, the "inorganic filler content" shown in Table 1 indicates the content of component (C) when the resin component in the resin composition is taken as 100 mass %. Furthermore, α represents the average linear thermal expansion coefficient, T represents a predetermined temperature, E' represents the storage modulus at the predetermined temperature T, n represents the crosslink density, Z f represents the average linear thermal expansion coefficient α divided by the storage modulus E′ at a given temperature T, and Tg represents the glass transition temperature.

[0246] [Table 1]

[0247] <Consideration> As can be seen from Table 1, by comparing the Examples and Comparative Examples, in the Examples, in the resin compositions containing the (A) and (B) components, the average linear thermal expansion coefficient α (ppm / K) of the cured product was calculated based on the crosslink density n (mol / cm 3 ) divided by Z f (ppm cm 3 / mol K) is expressed by the following formula: 145 <Z f <1300 It has been found that by satisfying these conditions, it is possible to provide a resin composition which suppresses warping and enables the production of a cured product having excellent long-term reliability.

[0248] Furthermore, the value Z f It was also found that by satisfying the above formula, it is possible to provide a resin composition capable of obtaining a cured product having excellent chemical resistance. It was also found that it is possible to provide a cured product of the resin composition according to the embodiment, a cured product of the resin composition, a resin sheet, a printed wiring board, a semiconductor chip package, and a semiconductor device.

[0249] In Examples 1 to 3, it was confirmed that even when the components (C) to (E) were not contained, the results were similar to those of the above Examples, although to a different extent. Also, in Examples 1 to 3, it was confirmed that even when the strong alkaline aqueous solution used to evaluate the chemical resistance was replaced by any of a tetramethylammonium hydroxide solution, a sodium hydroxide aqueous solution, and a sodium carbonate aqueous solution instead of a potassium hydroxide aqueous solution, the results were similar to those of the above Examples.

Claims

1. A resin composition comprising (A) an epoxy resin, (B) a curing agent, and (C) an inorganic filler, the content of the component (C) being 70 mass% or more when the total amount of non-volatile components in the resin composition is 100 mass%, The component (B) contains a maleimide compound represented by the following general formula (B2): 【Chemistry 1】 (In formula (B2), M 1 s each independently represent a divalent aliphatic hydrocarbon group containing an alkylene group having 5 or more carbon atoms which may have a substituent, A s each independently represent an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and t represents an integer from 1 to 10.) The resin composition was cured at 180° C. for 90 minutes to obtain a cured product having an average linear thermal expansion coefficient α (ppm / K) and a crosslink density n (mol / cm 3 ) divided by Z f (ppm cm 3 / mol·K) is represented by the following formula: 145<Z f <1300 The resin composition satisfies the above requirements.

2. The resin composition according to claim 1, wherein the aliphatic structure-containing maleimide compound comprises a maleimide compound represented by the following general formula (B2-1) or a maleimide compound represented by the following general formula (B2-2): 【Chemistry 2】 ... (B2-1) (In general formula (B2-1), M 2 and M. 3 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent; R 30 each independently represents an oxygen atom, an arylene group, an alkylene group, or a divalent group consisting of a combination of two or more of these groups; and t1 represents an integer of 1 to 10. 【Chemistry 3】 ... (B2-2) (In general formula (B2-2), M 4 , M. 6 and M. 7 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent; M 5 each independently represents a divalent group having an aromatic ring which may have a substituent; R 31 and R 32 each independently represents an alkyl group having 5 or more carbon atoms; t2 represents an integer of 0 to 10; and u1 and u2 each independently represent an integer of 0 to 4.

3. The resin composition according to claim 1 or 2, wherein the content of the component (B) is 0.5% by mass or more, based on 100% by mass of non-volatile components in the resin composition.

4. The resin composition according to any one of claims 1 to 3, further comprising (D) a thermoplastic resin.

5. The resin composition according to claim 4, wherein the component (D) has a functional group selected from the group consisting of a hydroxy group, a carboxy group, an amino group, a vinyl group, an acryloyl group, and a methacryloyl group.

6. The resin composition according to claim 4 or 5, wherein the content of the component (D) is 0.5% by mass or more and 25% by mass or less, based on 100% by mass of non-volatile components in the resin composition.

7. The resin composition according to any one of claims 1 to 6, wherein the average linear thermal expansion coefficient α of the cured product is 25 ppm / K or less.

8. The crosslink density n of the cured product is 0.15 mol / cm 3 The resin composition according to any one of claims 1 to 7, wherein:

9. The value Z f is expressed by the following formula: 150≦Z f ≦1000 The resin composition according to any one of claims 1 to 8, which satisfies the above.

10. The resin composition according to any one of claims 1 to 9, which is for forming an insulating layer.

11. The resin composition according to any one of claims 1 to 10, which is for forming a solder resist layer.

12. A cured product of the resin composition according to any one of claims 1 to 11.

13. A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 11.

14. A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of claims 1 to 11 or the cured product according to claim 12.

15. A semiconductor chip package comprising the printed wiring board according to claim 14 and a semiconductor chip mounted on the printed wiring board.

16. A semiconductor chip package comprising: a semiconductor chip; and a cured product of the resin composition according to any one of claims 1 to 11 or the cured product according to claim 12, which encapsulates the semiconductor chip.

17. A semiconductor device comprising the printed wiring board according to claim 14 or the semiconductor chip package according to claim 15 or 16.

Citation Information

Patent Citations

  • Resin composition

    JP2017125150A

  • Epoxy resin composition for sealing semiconductor, and semiconductor device

    JP2017179185A

  • Insulating material and electronic component

    JP2017188667A

  • Resin sheet

    JP2018041889A

  • Solid resin composition for sealing and rearrangement wafer therewith, semiconductor package, and production method thereof

    JP2018083893A